3’-sialyllactose inhibits the migration and invasion of LPS-induced B16F10 mouse melanoma cells through inactivation of the NF-KB signaling pathway - Hee-Do Kim; Hyunju-Choi; Yu-Chan Chang; Cheorl-Ho Kim (Glycoconjugate Journal, 2026)

Quantifying geothermal heat loss at the Dayoukeng crater using UAV thermal imaging and comparison with Landsat-derived estimates - Hai-Po Chan; Yu-Chang Chan; Cheng-Wei Sun (Geothermics, 2026)

Diethylenetriamine-directed selective formation of carbon-confined ultrafine MoO2 nanocrystals via one-pot spray pyrolysis for highly reversible and long-life Li-ion anodes - Jae Seob Lee; Do Won Jeong; Jin Ung Kim; K.C. Bhamu; Eun-Uk Yu; Jong-Ho Moon; Rakesh Saroha; Jin Koo Kim; Sang Mun Jeong; Gi Dae Park; Won-Jun Jang; Dong-Won Kang; et al. (Chemical Engineering Journal, 2026)

Non-destructive computer vision grading of Jin-Huang mango using texture and surface-blemish cues for packing-line quality control - Yung-Kuan Chan; Zih-Yan Ciou; Yu-Yi Chen; Chuen-Horng Lin; Jiunn-Lin Wu; Huan-Yu Chen (Journal of Food Engineering, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Cosolvent-driven exciton delocalization and dual dissociation pathways enable high-efficiency inverted all-polymer solar cells - Jia-Fu Chang; Hui Chan Ahn; Sunil V. Barma; Cheng-Yu Yeh; Yu-Cheng Tseng; Hyun Min Kwon; Hyerin Jeon; Hsu-Tzu Cheng; Bumjoon J. Kim; Sae Byeok Jo; Chu-Chen Chueh (Chemical Engineering Journal, 2026)

Mineral phase transformation drives molecular fractionation of dissolved organic matter during organic acid-driven weathering of bauxite residue - Chenglong Lu; Songlin Wu; Fang You; Dingyi Yu; Jitraporn Vongsvivut; Annaleise Klein; Lars Thomsen; David Parry; Ting-Shan Chan; Longbin Huang (Chemical Geology, 2026)

CD22+-apoptotic vesicles from cardiac fibroblasts provide endogenous cardioprotection against myocardial ischemia-reperfusion injury - Chan Zhang; Hao Hao; Nan Mu; Yishi Wang; Yin Yue; Lu Yu; Heng Ma (Science China Life Sciences, 2026)

Gamisoyo-san ameliorates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease in mice by modulating the SIRT1–AMPK–NRF2 pathway - Ye-Lim Kim; Hyo-Jeong Jin; Jong Seong Roh; Seokyung Park; Yu-Ri Seo; Sang-Chan Kim; Kwang Il Park; Phil Hyun Song; Chang-Hyun Song (Molecular & Cellular Toxicology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A systematic evaluation of key ingredient functionality on thermal and textural properties of plant-based cheese analogues - Huey Yu Lee; Eldwin Ze Hao Ooi; Shi Cheng Tong; Camille Keisha Mahendra; Eng-Seng Chan; Yee-Ying Lee (Food Chemistry, 2026)

Metabolic pathway for aerobic methane production in Burkholderia sp. HQL 1813 - Zeqin Liu; Zhengzheng Zhao; Zilong Cheng; Shiqi Xu; Xiaoyu Zhang; Spencer R. Moller; Minmin Cai; Ruth Elaine Blake; Chan Yu (Chemical Engineering Journal, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Design of heterogeneous core-shell structured Ni-incorporated MnOOH enclosed CoCe carbonate hydroxide network for ultrahigh-capacity supercapacitors - Anki Reddy Mule; Bhimanaboina Ramulu; Shaik Junied Arbaz; Chan-Hwa Chung; Jae Su Yu (Chemical Engineering Journal, 2026)

Fat on Fire: Disrupted Microglial Lipid Metabolism as a Driver of Anesthetic Neurotoxicity - Yu-Jie Mou; Hai-Yue Tu; Yi-Chan Wang; Shao-Yong Song; Hua-Yue Liu; Dong Wang; Jun-Chao Wu; Xiao-Wen Meng; Zheng-Hong Qin; Fu-Hai Ji (Neuroscience Bulletin, 2026)

A Dataset of Tropical Cyclones in the Western North Pacific from Chinese Fengyun Geostationary Meteorological Satellite Observations over the Past Two Decades - Xiaoqin Lu; Johnny C. L. Chan; Jie Tang; Hui Yu; Feng Lu; Yue Wang; Ming Ying; Runling Yu; Lan Wei; Longping Hu (Advances in Atmospheric Sciences, 2026)
This paper introduces a comprehensive Tropical Cyclone (TC) dataset based on China’s FengYun (FY) series geostationary satellite observations in the Western North Pacific (WNP), designated as FYSATTY. This innovative dataset integrates high-resolution geostationary meteorological satellite observations with best-track data, providing a unique resource for TC monitoring and analysis in the WNP region. FYSATTY is derived from infrared, water vapor, and visible channel imagery captured by the FY-2 and FY-4 satellites, which is processed using an equal-interval latitude-longitude grid system within a 1500-km radius centered on each TC. The best-track data, sourced from the China Meteorological Administration (CMA), is interpolated into 3-h intervals to ensure temporal consistency with the satellite observations. This dataset consists of 99714 observations for 614 TCs from 2005 to 2024 and will be updated annually. It represents the most comprehensive collection of TC satellite imagery derived from the FY series of geostationary meteorological satellites of the National Satellite Meteorological Center (NSMC). It encompasses a synthesis of infrared, water vapor, and visible channel data from the FY-2 and FY-4 satellite series. The dataset has been meticulously cropped and georeferenced using the CMA best-track data, with fundamental geographic spatial calibration completed. Comparative analysis with analogous elements within other TC geostationary meteorological satellite datasets reveals a high degree of consistency. It is suitable for reanalyzing TC best-track data, assessing climatic characteristics of TC satellite observations, and enhancing forecasting capabilities. This dataset is particularly useful for TC research, forecasting, and machine learning, and is publicly available.

Matriptase proteolysis selectively drives disassembly and internalization of the claudin-7 complex while preserving E-cadherin - Yu-Ling A. Kao; He-Yu Huang; Yin S. Yu; Nanxi Huang; Ya-Chin Chan; Chen-Ray Lee; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2026)

Impact of high-pressure processing on the degradation kinetics and bioactivity of resveratrol - Wen-Chien Lu; Yu-Tsung Cheng; Yung-Jia Chan; Shu-Ju Chen; Yan-Zhen Wu; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Stacked quantum dot organic light-emitting diodes in an industrial-grade inkjet printing process - Byoung-Hwa Kwon; Jin-Wook Shin; Chul Woong Joo; Chan-mo Kang; Hyunsu Cho; Sukyung Choi; Yoonsung Yoo; Hyungwoo Suh; Dong-Kyun Shin; Jaeryul Yu; Yeon Soo Lee; Seongju Kim; et al. (Chemical Engineering Journal, 2026)

Invasive species detection in heritage sites using UAV-based hyperspectral imagery and patch-based deep learning - Ayano Aida; San Gwon; Hosik Choi; Jaeyong Lee; Sejong Yu; Choong-sik Kim; Chan Park (Landscape and Ecological Engineering, 2026)

A comprehensive review of applied crystallization methods in industrial waste recycling and perspectives toward advanced applications - Jong Beom Lee; Ga-Eun Kim; So-Yeon Kim; Byeong-Chan Park; Jun-Ho Cha; Ji-Won Kwak; Yu-Jin Kim; Ik-Pyo Hong; Young-Pyo Jeon; Sang Goo Jeon; Geon-Hee Kim; Young Durk Park; et al. (Journal of Environmental Chemical Engineering, 2026)

Four new species of the little-known genus Baccalaureus Broch, 1929 (Thecostraca: Ascothoracida) endoparasitic in zoantharians from Taiwan: integrative taxonomy, functional morphology, diversity, and distribution - Gregory A. Kolbasov; Yao-Feng Tsao; Alexandra S. Savchenko; Meng-Chen Yu; Benny K. K. Chan (Marine Biodiversity, 2026)
Baccalaureus is a genus of specialized ascothoracidan endoparasites that inhabit the gastral cavity of zoantharian corals. Twelve species have been recognized in the genus. The present study, employing an integrative taxonomic approach, examines both the morphological and molecular divergence of Baccalaureus specimens collected from Palythoa corals in Taiwan. This analysis reveals four new species: Baccalaureus oliviformis sp. nov., Baccalaureus brevipes sp. nov., Baccalaureus arietinus sp. nov., and Baccalaureus spiralis sp. nov. These species are diagnosed based on the morphology of the carapace, paired thoracopods, penis rudiment, and furcal rami. Based on sequence divergence in COI and the results obtained from automatic partitioning analysis (ASAP) and Poisson tree processes (PTP) model methods, the samples of Baccalaureus collected in Taiwan were assigned to four or six groups. Diagnostic morphological characters for Baccalaureus include carapace shape, the structure of anterior thoracic horns, furcal rami, thoracopods 1, 5, and 6, and the development of seminal papillae and the penis rudiment. The study also compares host specificity interactions among members of the family Lauridae, including the genera Baccalaureus , Laura , Polymarsypus , and Zoanthoecus , offering new insights into the biology of these parasitic crustaceans. Previous records of all these zoantharian-infesting genera with localities, depths, and host taxonomy are summarized, showing the diversity of host taxa, wide geographical, and vertical ranges of the parasites.

Redox contrast of W at EuWO4/W interfaces promotes polysulfide conversion in lithium–sulfur batteries - Fushuai Yu; Chan Wang; Xiaoyu Chen; Changheng Yang; Junfeng Hui; Xiaoyan Zheng; Huigang Zhang; Dong Li; Qingshan Zhu (Chemical Engineering Journal, 2026)

Comparison of mono- and co-digestion of moderately thermo-alkaline pretreated sewage sludge with food waste: Effects on methane production and microbial communities - Lijun Luo; Tung Tung Chan; Giin Yu Amy Tan; Francesco Di Capua; Nirakar Pradhan (Biomass and Bioenergy, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Towards spatial equality in China’s protected area system: An assessment framework integrating accessibility and availability - Zhangqian Ye; Yue Cao; Yunshuang Feng; Ming Yam Chan; Haimeng Liu; Xiaoqing Xu; Chengzhao Wu; Bin Chen; Le Yu; Zhicong Zhao; Pei Wang; Shiquan Zhao; et al. (Landscape and Urban Planning, 2026)

Facile synthesis of Cu2O/hydrochar composites achieving high-efficiency antibiotic capture in bioretention column - Yanji Huang; Yidan Luo; Hailong Zhang; Yuanwang Lan; Pingrui Wang; Shuohan Yu; Kai Yu; Mingshan Xue; Chan Xie; Zuozhu Yin; Bin Gao (Environmental Research, 2026)

Flame-retardant liquid metal in cellulose/MXene fire warning sensors - Yu Lei; Lulu Xu; Yuan Xien Lee; Yan Zhang; Yao Yuan; Anthony C.Y. Yuen; Vipul Agarwal; Kate T.Q. Nguyen; Guan Heng Yeoh; Cheng Wang; Qing Nian Chan; Wei Wang (Chemical Engineering Journal, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Dual-Drug Stent with Sirolimus and WKYMVm Promotes Endothelialization and Limits Hyperplasia - Yu Jeong Jin; Dae Sung Park; Myung Ho Jeong; Doo Sun Sim; Mi Hyang Na; Chan Woo Kim; Jeong Ha Kim; Hae Jin Kee; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2026)

Coupling 1D-2D hydrodynamic model for urban flooding simulation based on multi-faceted data in Hong Kong - Man Hong Chiu; Xinyu Yu; Huan-Feng Duan; Man Sing Wong; Onyx Wing Hong Wai; PW Chan; Yifan Luo (Natural Hazards, 2026)
Flooding has intensified due to climate change and rapid urbanisation. Extensive studies have been conducted to simulate flooding of outdoor environment. However, limited studies have been conducted inintegrating outdoor and indoor flooding risk assessment. Therefore, this study adopted Infowork ICM model and integrated multi-facted data, including open-sourced drainage networks, 3D visualisation maps, territory habitat maps, raingauge data and minute-interval Kai Tak river level data from monitoring stations provided by the Drainage Service Department to examine and identify risky outdoor and indoor areas under extreme rainfall based on simulated scenarios. The study area is the part of the Kowloon East Area. Specifically, two rainfall scenarios, with different return periods and durations (the index quantifying the severity of rainfall), have been designed and analysed. The RMSE is 45 mm. The simulated result reveals that 15.0%, 25.1% and 27.2% of the study area suffered flooding higher than 100 mm in rainfall events with return periods of 2, 200 and 1000 years respectively. 18.6%, 27% and 28.2% of the study area suffered flooding higher than 250 mm in rainfall events with duration of 60, 180 and 300 min respectively. Moreover, results indicate that flooding is centralised in Kowloon Bay Area, Lung Cheong Road, Kai Yip Estate and Choi Hung Estate. The simulation-based flooding assessment framework provided a basis for investigating spatial-temporal patterns and conducting risk assessment of frequent flooding.

Protective effects of sodium benzoate against toluene-induced reward enhancement, behavioral disturbances, and impaired synaptic plasticity in mice - Chung-Pin Hsieh; Mei-Yi Lee; Chia-Yu Lin; Ming-Huan Chan; Hwei-Hsien Chen (NeuroToxicology, 2026)

Strain-specific gut microbiota modulation is linked to resistance to BmNPV infection in silkworms - Fareed Uddin Memon; Jing Xu; Xiaole Xie; Chan Shu; Yu Li; Kang Li; Yang Xiao; Ling Tian (Journal of Invertebrate Pathology, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Toxic effects of microplastic (polyethylene) exposure: Stress, immune responses and neurotoxicity in crucian carp, Carassius carassius - Young-Bin Yu; A-Hyun Jo; Cheol Young Choi; Ju-Chan Kang; Jun-Hwan Kim (Fish & Shellfish Immunology, 2026)

PM2.5-modulated targets and miRNAs associated with lung cancer and injury are protected by natural products - Ya-Ting Chuang; Ching-Yu Yen; Wangta Liu; Fang-Rong Chang; Yi-Hong Tsai; Wen-Hsiung Chan; Tsu-Ming Chien; Hsueh-Wei Chang (Environmental Pollution, 2026)

Functional microbial consortia augmented black soldier fly larvae achieve high efficiency ammonia mitigation during chicken manure bioconversion - Zhengzheng Zhao; Yan Ju; Bingqi Gao; Yongqiang Yu; Kashif ur Rehman; Núria Jiménez; Pablo Gago-Ferrero; Jessica Subirats; Víctor Matamoros; Dingmei Wang; Qinfen Li; Longyu Zheng; et al. (Bioresource Technology, 2026)

TEDD 2.0: an advanced temporal gene expression database enabled by in-silico functional analyses for developmental mechanism investigation - Chi Chun Chan; King Kin Lam; Lin Chen; Mingyang Yu; Jingwen Hu; Yujie Zhu; Yuting Zheng; Jia Zheng; Kwong Wai Choy; Zirui Dong (Science China Life Sciences, 2026)

Effect of oxygen-containing functional groups on selenium removal by the carbonaceous adsorbent from MSW incineration flue gas - Shuaijie Yu; Shuai Li; Hongyun Hu; Linxia Gao; Zhong Lin; Chan Zou; Lu Dong; Yongda Huang; Hong Yao (Fuel, 2026)

Catalytic hairpin assembly-assisted dual-enhanced SERS satellite nanocomplex for ultrasensitive detection of lipopolysaccharides in injection samples - Chan Huang; Xiuying Li; Xuan Zeng; Lingzhi Chen; Huabin Zhang; Xinjie Guo; Yiqun Chang; Wenshi Huang; Yichu Nie; Tianen Zhou; Jiaqi Yu; Jun Xu; et al. (Chemical Engineering Journal, 2026)

Economically feasible and carbon-negative emission disposal of saline wastewater: Concentration-electrolysis integrating waste heat recovery and co-disposal of industrial waste salt - Xiaoyang Chen; Yuhai He; Ting Zhao; Peixiong Tan; Naizhen Yu; Chan Zou; Yipeng Wang; Huimin Liu (Chemical Engineering Journal, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Auditory-perception-based tuneable noise control approach for improving acoustic comfort and behaviour of autistic individuals in indoor/outdoor environments - Tak Chun Kwong; Steve Wai Yin Mung; Huan-Ling Yuan; Henry Kar Hang Chu; Yuen Yi Cynthia Lai; Chetwyn Che Hin Chan; Ho Man Yu; Yat Sze Choy (Building and Environment, 2026)

β-Caryophyllene Induces PPARγ-Mediated Apoptosis and Enhances the Radiosensitivity in Colorectal Cancer Cells - Hui-Wen Chan; Deng-Yu Kuo; Yu-Chieh Jill Kao; Yun-Xuan Tang; Hui-Yen Chuang (Journal of Medical and Biological Engineering, 2026)
Purpose This study aimed to investigate the radiosensitizing potential of β-caryophyllene (BCP), a natural CB2 receptor agonist, in colorectal cancer (CRC) cells and to elucidate the underlying molecular mechanisms. Methods Murine CT26 and human HCT116 CRC cells were treated with BCP alone or in combination with radiotherapy (RT). Cell viability was evaluated using the MTT assay, and combination index (CI) values were calculated to assess synergy. Flow cytometry and immunofluorescence were used to analyze cell cycle distribution and DNA damage. Protein expression levels of PPARγ, phosphorylated AKT (pAKT), cyclin D1, Bax, Bcl-2, and cleaved caspase-3 were examined by western blot. Results BCP synergistically enhanced RT-induced cytotoxicity in both CRC cell lines, with CI values ranging from 0.92 to 0.70 in CT26 cells and from 0.78 to 0.68 in HCT116 cells at 4 and 8 Gy irradiation. The combination treatment resulted in significant G2/M arrest and sustained γH2AX expression at both 24 and 48 h, indicating persistent DNA double-strand breaks. BCP suppressed pAKT and cyclin D1 levels while upregulated PPARγ expression. Activated apoptosis was verified by increased Bax/Bcl-2 ratios and elevated cleaved caspase-3 levels. Conclusion BCP enhances the radiosensitivity of CRC cells by promoting RT-induced DNA damage and triggering PPARγ-mediated apoptotic pathways. These findings support its potential as a natural radiosensitizer in CRC treatment.

Psychometric evaluation of a modified food security survey scale in the economically deprived population of Hong Kong - Ka Yu Kwan; Pui Hing Chau; Mandy Ho; Chee Hon Chan; Raymond Lap Ming Tang; Paul Siu Fai Yip (Food Security, 2026)
Food security is vital for global health and sustainable development. However, existing validated versions of the Household Food Security Survey Module (HFSSM) cannot address the needs for a shorter Chinese version with a shorter reference period. This study aimed to examine the psychometric properties of a 6-item Chinese-version of the HFSSM (3-month reference period), among the economically deprived population in Hong Kong. This study included 512 observations from community-dwelling Chinese adults (≥ 18 years), who were social services users or food assistant service applicants, and with household income < 75% of the population median. Construct validity and scale targeting were assessed using Rasch analysis. Convergent validity, known-group validity, internal consistency, and test-retest reliability were also examined. The construct validity was satisfactory, with a logical item calibration hierarchy and good infit statistics for five items (0.81–1.26), although a floor effect was indicated in the Wright map. The convergent validity was supported through a moderate positive correlation with the single-item household food insufficiency scale ( r = 0.58). Known-group validity showed higher scores among those aged < 65 years (d = 1.17, p < 0.001), living with children aged < 18 years (d = 1.09, p < 0.001), enrolled in the food assistance program (d = 0.54, p < 0.001), living at the poverty line or below (d = 0.30, p = 0.010), and with poor or fair health (d = 0.20, p = 0.028). Furthermore, the scale had fair-to-good internal consistency (Cronbach’s alpha = 0.88, Rasch person reliability = 0.64) and excellent test-retest reliability (ICC = 0.96) in one week. The 6-item Chinese-version of the HFSSM (3-month reference period) is a valid and reliable measure of household food insecurity in the economically deprived population in Hong Kong.

Establishment of in vitro callus culture and analysis of Bakuchiol from Cullen corylifolium - Na-Gyeol Hwang; Chan-Woo Park; Ye-Rin Kim; Hyo-Jeong Kim; Ji-Hyun Kim; Eunbeen Shin; Seon Beom Kim; Yeongju Lee; Dae Youn Hwang; Sunho Park; Eun Sang Jung; Yu-Jin Kim (Plant Biotechnology Reports, 2026)

Oblique Wave Scattering by a Floating Rectangular Porous Box with an Impermeable Bottom - Yu-Chan Guo; Sarat Chandra Mohapatra; C. Guedes Soares (Journal of Marine Science and Engineering, 2026)
Based on linear wave theory and potential flow theory, the wave scattering performance of a rectangular floating porous box with an impermeable bottom is investigated analytically. The mathematical formulation of the physical problem is well established and solved, and its analytical solutions are appropriately obtained using the matched eigenfunction expansion method. The convergency and accuracy of the analytical solutions are carefully verified and thoroughly validated. It is found that the present analytical solutions converge up to three decimal places and agree well with the numerical results published in the previous literature. Furthermore, important numerical results are calculated to thoroughly analyze the oblique wave scattering performance of the proposed rectangular floating porous box with an impermeable bottom and its efficiency in preventing incident waves when used as a floating breakwater. It is concluded that the dimensionless width (L/h), submergence depth (d/h), and frictional coefficient (f) have a significant influence on the scattering performance and the transmission coefficient of the proposed porous box. This work is beneficial for the design and future development of floating rectangular porous box breakwaters.

Unravelling the street thermal features network and spatial visual thermal inertia: A study in Hong Kong - Kang Zou; Man Sing Wong; Majid Nazeer; Xinyu Yu; Gangyi Tan; Huiying (Cynthia) Hou; Jinxin Yang; Pak Wai Chan (Sustainable Cities and Society, 2026)

E-cigarette vapor alters gut microbiota composition in zebrafish - Thi Ngoc Mai Dong; Delbert Almerick T. Boncan; Carl Andersen Macaraeg Tan; Da-Wei Liu; Hsin-Yu Sun; Ting-Wei Huang; Chen Hsu; Kuo-Chang Chu; Zulvikar Syambani Ulhaq; Keng Po Lai; Douglas Robert Drummond; Yukiko Ogino; et al. (Science of The Total Environment, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Observational study of atmospheric boundary layer height in Hong Kong based on 20-year multi-source measurements - Yu-Cheng Xue; Jun-Yi He; Pak-Wai Chan; Qiu-Sheng Li (Atmospheric Research, 2026)

Exosome Purification Strategy Influences the Regenerative Efficacy of Dental Pulp Stem Cell-Derived Exosomes in Bone Regeneration - Borae Lee; Chia-Yi Hung; Yu-Ting Chien; Chi-Che Hsieh; Wei-Hao Cheng; Ya-Hui Chan; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2026)

Craniofacial photography for detection of positional obstructive sleep apnoea - Kate Sutherland; John Wheatley; Kristina Kairaitis; Brendon J. Yee; Gary Cohen; Kerri Melehan; Stephen Lambert; Philip de Chazal; Peter A. Cistulli; Peter Cistulli; Philip de Chazal; Nina Sarkissian; et al. (Sleep and Biological Rhythms, 2026)
Supine-dependent OSA is a well-recognised OSA phenotype and may relate to craniofacial structure. Our aim was to assess whether craniofacial photos are able to identify positional OSA, specifically supine-isolated OSA, in comparison to non-positional OSA. Frontal and profile craniofacial photographs of participants were acquired according to a standardised protocol. Photographs were analysed and compared between non-positional and supine-isolated OSA groups. A total of 156 OSA patients were included (54.5% supine-isolated OSA, 45.5% with non-positional OSA). The supine-isolated group had a longer upper face height and greater upper-to-lower face height ratio, smaller face width, reduced face width-to-height ratio, and smaller mandibular width, length, and size of the mandibular base. Differences in facial measurements were no longer significant after adjustment for body size and OSA severity. Our study demonstrates that supine-isolated OSA can be identified using facial photography. Larger studies in groups matched for BMI and OSA severity are needed to confirm whether this technique may also capture other features related to supine-isolated OSA (i.e., differences in underlying skeletal structure).

Suppression of Inflammatory Responses Through GD3 Synthase (GD3S) Silencing Mediated by TLR4 Signaling: In Vitro and In Silico Analysis - Jun-Young Park; Abekura Fukushi; Hee-Do Kim; Han-His Kuo; Yu-Chan Chang; Daeui Park; Cheorl-Ho Kim (Molecular Neurobiology, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

APOE Lipoprotein Particles: Pathophysiology, Therapy, and the Crosstalk in Alzheimer’s Disease and Cardiovascular Disease - Chan Liu; Juan Liu; Yan-Yang Wang; Shang-Fu Xu; Li-Mei Yu (Molecular Neurobiology, 2026)

Arsenic species exposure and urinary metabolic profiling in children and elderly residents near a petrochemical complex in Taiwan - Tzu-Hsuen Yuan; Yi-Ting Hsieh; Chi-Hsin Chen; Chia-Yu Chang; Chang-Chuan Chan (Environmental Geochemistry and Health, 2026)

Global Molecular Taxonomy, Phylogeny and Biogeography of the Clam Genus Corbicula (Bivalvia: Cyrenidae) - Yulia V. Bespalaya; Alexander V. Kropotin; Olga V. Aksenova; Mikhail Yu. Gofarov; Alexander V. Kondakov; Ekaterina S. Konopleva; Irina S. Khrebtova; Youness Mabrouki; Dmitry M. Palatov; Alexander A. Prokin; Dmitry P. Karabanov; Oksana V. Travina; et al. (Zoologica Scripta, 2026)
The Corbicula clams (Bivalvia: Cyrenidae) are an ecologically significant and widespread group of fresh‐ and brackish‐water molluscs, playing a keystone role in aquatic ecosystems. Some species of this genus are subglobal invaders. The taxonomy of Corbicula remains very confusing, which hinders both fundamental and applied research on this genus. A comprehensive revision of the taxonomic structure of this group has been lacking so far. In this paper, we clarify the taxonomy, distribution, and evolutionary biogeography of the living representatives of the genus Corbicula , including species widely distributed in their non‐native ranges, on the basis of the largest dataset of DNA sequences ever analysed. Our data reveal that the genus Corbicula contains two subgenus‐level clades: Corbicula s.s. and Sphaerocorbicula Bolotov, Bespalaya & Aksenova subgen. nov. Our COI mtDNA and two‐locus phylogenies reveal that the genus Corbicula contains not Corbicula bilini Bespalaya, Kropotin, Kondakov, Konopleva & Bolotov sp. nov. (Bilin River, Myanmar) and C. lemroae Bespalaya, Kropotin, Kondakov, Konopleva & Bolotov sp. nov. (Lemro River, Myanmar). A new synonymy is established for five species of Corbicula and one is transferred from the family Sphaeriidae to Cyrenidae. Our fossil‐calibrated phylogeny and generalised biogeographic model indicate that the most recent common ancestor of the genus Corbicula could have originated somewhere within a broad area covering Asia near the upper boundary of the Middle Cretaceous.

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Synergistic transgenerational reproductive toxicity of polystyrene nanoplastics and butylparaben at NOAEL levels via SET-2–mediated H3K4me3 modification in Caenorhabditis elegans - Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Journal of Hazardous Materials, 2025)

Black soldier fly organic fertilizer restricts the mobility of soil Pseudomonas to mitigate vertical migration of antibiotic resistance genes in agricultural systems - Zhengzheng Zhao; Bingqi Gao; Yijie Ma; Xuemeng Wang; Núria Jiménez; Jessica Subirats; Dingmei Wang; Qinfen Li; Joshua WK Ho; Yan Xue; Jianfeng Wu; Longyu Zheng; et al. (Journal of Environmental Chemical Engineering, 2025)

The mechanical, optical and barrier properties of antimicrobial films based on composite essential oil microcapsules and their effects on the preservation and physicochemical properties of cherry tomatoes - Zaixiang Lou; Hongwei Tao; Jiayu Yu; Xinyan Cui; Sookwah Chan (Food Bioscience, 2025)

Silver nanoparticles incorporated, yellow turmeric extract-infused polycaprolactone/starch electrospun nanofibers: Synthesis, physiochemical characterization, and fruit-packaging behavior - Ganesh Prasad Awasthi; Miyeon Shin; Krishna Prasad Sharma; Richa Jaswal; Rabin K.C.; Rajendra Bahadur G.C.; Chan Hee Park; Mahesh kumar Joshi; Changho Yu (Food Packaging and Shelf Life, 2025)

Exposome-wide associations and polyexposure risks of workplace chemical exposures on adult asthma: The Personalized Environment and Genes Study (PEGS) - Yujing Chen; Farida S. Akhtari; Yixuan He; Lihang Yu; Vy Kim Nguyen; Martin Tsz-Ki Tsui; Yuki Mizuno; William E. Funk; Crystal Ying Chan; Lap Ah Tse; Kin Fai Ho; Chirag J. Patel; et al. (Environmental Research, 2025)

Effects of chicken manure-derived black soldier fly organic fertilizer on soil carbon and nitrogen cycling: insights from metagenomic and microbial network analysis - Zhengzheng Zhao; Bingqi Gao; Ahmed R. Henawy; Kashif ur Rehman; Joshua WK. Ho; Yan Xue; Jianfeng Wu; Núria Jiménez; Jessica Subirats; Longyu Zheng; Feng Huang; Chan Yu; et al. (Environmental Research, 2025)

Alternative seismic details with hook-confining clips for SRC columns: Cyclic loading test and numerical simulation - Hyun-Soo Youm; Yu-Bin Kim; Chan-Hyun Park; Kyoung-Yeun Park; Yong-Joo Kim; Dae-Jin Kim (Engineering Structures, 2025)

Photothermal nanomedicine for glioblastoma: From material design to clinical translation challenges - Chan Li; Hui-Zhe Xu; Xue-Yan Cheng; Xin Yu; Zhi-Qiang Gong; Yi-Jiang He; Ling-Xiao Zhao; Zhan-You Wang (Chemical Engineering Journal, 2025)

Self-limiting low-temperature growth of high-quality monolayer graphene by synergistic effects of pyrene, CH4, and Cu vapor - Yu Min Kim; Hyo Chan Hong; Yongjun Yang; Seungjae Moon; Dalsu Choi; Hyo Chan Lee (Chemical Engineering Journal, 2025)

Rapid detection of transgene insertion patterns in living modified Phalaenopsis via inverse PCR and nanopore sequencing validated against Illumina and PacBio sequencing platforms - Yu Kyong Hu; Jun-Kyung Lee; Yong-Gil Shin; Byoung-Eun Min; Ki‐Hong Jung; Chan Hui Lee; Sun-Goo Hwang; Sung Don Lim (Plant Biotechnology Reports, 2025)

Investigation of Aviation Turbulence in Different Air Traffic Control Zones across China - Jingyuan Shao; Zhenyu Yu; Yi Li; Kaijun Wu; Zhaoyue Zhang; Youfan Chen; Wenhan Gu; Haiwen Liu; Yanyu Leung; Pak-Wai Chan; Jianping Guo; Zibo Zhuang (Journal of Meteorological Research, 2025)

Downlisting and recovery of species assessed by the IUCN - Mu‐Ming Lin; Richard A. Fuller; In‐Ki Kwon; Kisup Lee; Simba Chan; Wangwang Qiu; Yat‐Tung Yu; Chi‐Yeung Choi (Conservation Biology, 2025)
Despite the increasing number of species assessed for extinction risk by the International Union for Conservation of Nature (IUCN) (163,040 species as of 2024), only about 1 in 1,000 have been downlisted due to genuine population improvement. Although this rare conservation achievement has been widely celebrated in several recent cases, some other downlisting decisions have met with controversy. A primary role of the IUCN is to assess extinction risk. In this role, it must maintain its independence and not be influenced by the public outcry that may occur when a high‐profile species is downlisted, even if well‐established conservation programs may be disrupted or abandoned as a result. We explored the potential positive and negative consequences of downlisting for conservation efforts through case studies of the giant panda ( Ailuropoda melanoleuca ), red‐crowned crane ( Grus japonensis ), saiga antelope ( Saiga tatarica ), and black‐faced spoonbill ( Platalea minor ), which has recently been proposed for downlisting. Although downlisting can enable more effective use of limited resources, these cases highlight potential risks, including weakened legal backing, diversion of resources away from the species, and declining public and political support. The relatively unquestioned downlisting of the saiga antelope illustrates how early and inclusive engagement of local experts, assessors, donors, and other stakeholders can help ensure that decisions are effectively communicated and implemented without jeopardizing species recovery. The IUCN Green Status of Species assessment is a complementary tool to the IUCN Red List and offers a useful measure of conservation progress, which can help decision makers ensure that downlisting does not undermine long‐term conservation efforts.

Disentangling the anthropogenic and environmental correlates of microplastic pollution in the coastal waters of a metropolis in Southern China - Pengfei Wu; Yu Zhao; Ngai Kwan Chan; Jian-Wen Qiu; Zongwei Cai (Environmental Pollution, 2025)

A Li-ion permeable poly(phenylene ether-ether-sulfone) interphase to address interfacial instability and structural degradation of Ni-rich NCM cathodes in poly(ethylene oxide)-based all-solid-state Li-ion batteries - Cheng-Hung Liao; Yu-Ting Weng; Senthil-Kumar Parthasarathi; Hsi Chen; Shu-Jui Chang; Guan-Yi Liu; Tsung-Yu Yu; Chih-Wen Pao; Ting-Shan Chan; Wei-Tsung Chuang; Chun-Chieh Wang; Ru-Jong Jeng; et al. (Chemical Engineering Journal, 2025)

WITHDRAWN: Structure-activity relationship of oligosaccharides derived from Bletilla striata polysaccharides and wound healing promotion efficacy of its hydrogels - Jie Tang; Chan Jin; Jingjing Yu; Zhixuan Li; Chaoyue Zhao; Qingxiang Guan (Carbohydrate Polymers, 2025)

Synergistic mechanism of tetracycline degradation by poor-degrading microbe Serratia marcescens cooperated with insect during environmental decomposition cycle - Chongrui Yang; Zhengzheng Zhao; Chen Sun; Bingqi Gao; Yushi Wu; Mengzhe Li; Liu Chen; Yan Ju; Kashif ur Rehman; Chan Yu; Qinfen Li; Arnold van Huis; et al. (Bioresource Technology, 2025)

Streptococcus atopica sp. nov., Isolated from the Feces of a Toddler with Atopic Dermatitis - Chin-Kan Chan; Hui-Shan Wu; Li-Jyun Tsai; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yi-Sheng Chen (Current Microbiology, 2025)

Long noncoding RNAs as molecular architects: Shaping plant functions and physiological plasticity - Yu-Chan Zhang; Re-Qing He; Yu Cheng; Dong Wang; Federico Ariel; Yue-Qin Chen (Molecular Plant, 2025)

Simultaneous carrier concentration regulation and grain boundary passivation enable over 14 % efficient Ag-alloyed kesterite solar cells - Mengyang Wang; Yu Mao; Wenjian Chan; Yuanyuan Huang; Yanmei Deng; Ziyang Ren; Ening Gu; Xianzhong Lin; Guowei Yang (Chemical Engineering Journal, 2025)

Stretchable electrochromic organogels using photo-crosslinkable fluoran dye-based platform for wearable electronics - Chan Young Kim; Gimin Sung; Jeong-Yun Sun; Woong-Ryeol Yu (Chemical Engineering Journal, 2025)

Cerebellar Stimulation Modulates Reward Processing: A High-definition Transcranial Direct Current Stimulation Study - Xuan Wang; Jin-ting Yu; Ling-ling Wang; Jia Huang; Yi Wang; Simon S. Y. Lui; Raymond C. K. Chan (The Cerebellum, 2025)

Furosemide sodium enhanced AQP3 expression by inhibiting NKCC1 leading to improved vitrification freezing rates of mouse and bovine blastocysts - Chang-Guo Min; Xue-Song Shan; Kai-Yan Zhang; Yu-Chan Wang; Xin Ma; Jun Wang; Jing Zhao; Yi Fang; Hong-Yu Liu; He Ding; Dian Wang; Jing Guo; et al. (Theriogenology, 2025)

Enhanced iodide sorption onto montmorillonite via interlayer ion-pairing with calcium - Seonggyu Choi; Yongheum Jo; Ja-Young Goo; Sol-Chan Han; Seonyi Namgung; Song-I Yu; Sang-Ho Lee (Journal of Hazardous Materials, 2025)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Early-life indoor environmental exposures and COVID-19 outcomes in Chinese preschool children: A secondary analysis of a multicenter study - Chan Lu; Jing Ma; Zipeng Qiao; Yichen Yu; Wanxue Xu; Wewei Liu; Faming Wang (Journal of Hazardous Materials, 2025)

Spatiotemporal dynamics of histone H3K27 demethylase during development - Yu-Chen Tsai; Yun-Chen Chung; Cheng-Chan Yang; Cheng-Hsien Lee; Che-Wei Liu; Shih-Ming Huang; Lan-Hsin Wang (Insect Biochemistry and Molecular Biology, 2025)

The correlation of immunotoxicity with size and chemical properties of particulate matter within macrophages - Hsiang-Yu Kung; Yi-Shiuan Wang; Yung-Jui Chen; Ting-Hsuan Wu; Jai-Yu Chen; Yueh-Feng Wen; Yu-Cheng Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Realizing practical use of LiNiO2 cathode in halide-based all-solid-state lithium metal batteries - Hsi Chen; Hao-Wen Liu; Yu-Cheng Lu; Pei-Jane Yu; Cheng-Hung Liao; Chun-Chieh Wang; Ting-Shan Chan; Hwo-Shuenn Sheu; Po-Ya Chang; Jeng-Lung Chen; Shu-Chih Haw; Gung-Chian Yin; et al. (Chemical Engineering Journal, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Latent Growth Models of Longitudinal Changes in Functional Connectivity during Early Stage Psychosis - Kristina M. Holton; Shi Yu Chan; Austin J. Brockmeier; Mei-Hua Hall (Neuroinformatics, 2025)

Integrating track layout into urban rail vulnerability envelope assessment: A case of Hong Kong rail transit network - Yingying Xu; Yu Gu; Ho-Yin Chan; Yi-Qing Ni; Anthony Chen (Journal of Transport Geography, 2025)

Mitigating the vertical migration and leaching risks of antibiotic resistance genes through insect fertilizer application - Zhengzheng Zhao; Bingqi Gao; Gen Li; Huanhuan Yang; Jiasheng Guo; Longyu Zheng; Feng Huang; Ziniu Yu; Chan Yu; Jibin Zhang; Minmin Cai (Environmental Research, 2025)

Size Characteristics of Tropical Cyclones Affecting East China and Those in the Western North Pacific - Xiaoqin Lu; Johnny C. L. Chan; Ming Ying; Hui Yu (Advances in Atmospheric Sciences, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Higher bisphenol analogues exposure levels in e-waste workers and their associations with DNA oxidative damage in Hong Kong - Gengze Liao; Xueqiong Weng; Feng Wang; Yanny Hoi Kuen Yu; Samuel Yeung-shan Wong; Victoria H. Arrandale; Alan Hoi-shou Chan; Shaoyou Lu; Lap Ah Tse (Environmental Research, 2025)

Behaviour and modelling of concrete in circular hybrid multitube concrete columns - C.W. Chan; T. Yu; S.S. Zhang; W.C. Xue (Engineering Structures, 2025)

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Occurrence & characterization of Staphylococcus aureus from ready-to-eat (RTE), and cooked food in Singapore: A retrospective analysis - Ye Htut Zwe; Roshini Devi Mohan; Si Jia Lim; Wai Ching Lai; Kae Hwan Sim; Yu Lee Leyau; Ker Lew; Joachim Mun Choy Chua; Kyaw Thu Aung; Kern Rei Chng; Yuan Sheng Wu; Joanne Sheot Harn Chan; et al. (International Journal of Food Microbiology, 2025)

A hybrid domain adaptation approach for estimation of prestressed forces in prestressed concrete bridges under moving vehicles - Saeid Talaei; Xinqun Zhu; Jianchun Li; Yang Yu; Tommy H.T. Chan (Engineering Structures, 2025)

Highly efficient multifunctional 3D polyurethane sponge with photothermal responsiveness for efficient oil-water separation and microplastic extraction - Ritong Wang; Zuozhu Yin; Guoyan Yang; Qidong Zha; Cong Xiong; Yu Xie; Jilin Xu; Yidan Luo; Zhen Hong; Chan Xie; Mingshan Xue (Desalination, 2025)

Assessing ecosystem integrity in protected areas: A systematic review of methods and applications - Yunshuang Feng; Yue Cao; Ming Yam Chan; Zhangqian Ye; Zhicong Zhao; Le Yu; Yongliang Liang; Steve Carver; Rui Yang (Biological Conservation, 2025)

Monitoring slow-moving deep-seated landslide using PSI technique: a case study of a potential sliding slope from southern Taiwan - Abhishek Lakhote; Yu-Chang Chan; Chiao-Yin Lu; Gopal Kumar; Cheng-Wei Sun (Landslides, 2025)
Studying slow-moving, deep-seated landslides is crucial due to their long-lasting effects on landscapes, infrastructure, and communities. In mountainous regions like Taiwan, understanding these landslides is vital for hazard mitigation and land-use planning. Over 2500 pre-existing landslides have been cataloged in Taiwan using LiDAR data, with many identified as potential slow-moving landslide zones, including a significant site, the Liugui-D047, near Hsinfa Village in southern Taiwan. This study aims to understand the E-W and vertical deformation rates at the potential landslide site using the persistent scattering interferometry (PSI) technique. PSI is particularly effective for detecting slow-moving landslides, providing millimeter-level precision in surface deformation measurements over time. By utilizing open-source tools like ISCE and StaMPS, we conducted a five-year PSI analysis from 2018 to 2023 to monitor surface movements at the site. Our results revealed minimal deformation rates, with westward movements ranging from 4.1 to 2.2 mm/yr and vertical downward movements from 4.2 to 1.4 mm/yr. These findings were validated by in situ measurements collected in 2023, confirming the observations of PSI for long-term monitoring. This highlights the effectiveness of combining PSI techniques with open-source tools for monitoring landslide sites, especially in areas with limited in-situ resources. Our study shows that this integration can yield detailed, long-term insights into surface deformations while reducing the costs of extensive in-situ monitoring. Additionally, our findings indicate that the topographically well-defined Liugui-D047 landslide site remained stable with minimal movement over five years, though ongoing monitoring is essential due to multiple influencing factors.

Predicting Convectively Induced Turbulence With Regionally Convection-Permitting Simulations - Haoming Chen; Christy Yan-yu Leung; Ping Cheung; Haolin Liu; Sai Tick Chan; Xiaoming Shi (Asia-Pacific Journal of Atmospheric Sciences, 2025)
Convectively induced turbulence (CIT) is a severe aviation hazard. It is challenging to forecast CIT because low-resolution models cannot explicitly resolve convective motions at kilometer scales. In this study, we used the Model for Prediction Across Scales (MPAS) to simulate CIT cases with convection-permitting resolution ( $$\sim $$ ∼ 1 km) in the region of the CIT events and coarse resolution in other parts of the globe. We developed a method to estimate the eddy dissipation rate (EDR) using the resolved wind field of the MPAS simulations. The method is based on explicit filtering and reconstruction in the turbulence modeling for large-eddy simulations (LES). It estimates turbulence kinetic energy (TKE), which is then used to derive EDR. The new method produces different turbulence distribution and intensity than previous methods based on second-order structure functions and convective gravity wave drag, with higher accuracy and better correlation with observations for CIT cases tested in this study. The 1-km resolution simulation generates more accurate EDR and improves spatial patterns, but it is computationally demanding. The 3-km resolution can get benefits from reasonable accuracy and affordable computational cost. Because convection-permitting resolutions are in the gray zone for simulating convection, we evaluated the sensitivity of the prediction to the variations in physical and numerical schemes. Varying cumulus convection parameterization and monotonicity of numerical schemes are identified as practical approaches to generate beneficial ensemble spread. However, the physical perturbation-based ensemble has limitations, and initial condition perturbations are still necessary to encompass uncertainties in the development of convection.

Microplastics induce toxic effects in fish: Bioaccumulation, hematological parameters and antioxidant responses - A-Hyun Jo; Young-Bin Yu; Jae-Ho Choi; Ju-Hyeong Lee; Cheol Young Choi; Ju-Chan Kang; Jun-Hwan Kim (Chemosphere, 2025)

Development of a multiplex PCR assay for detection of Riemerella anatipestifer serotype 1 and serotype 2 strains - Mengsi Wu; Rong Guo; Meitong Chen; Min Zhu; Zongchao Chen; Chan Ding; Shengqing Yu (Veterinary Microbiology, 2025)

Changes in regulatory requirements for potency testing of snake antivenom in Korea - Wonjong Lee; Hyun Jeong Kim; Yu Jeong Oh; Su Kyoung Seong; Young Hoon Kim; Youngju Choi; Sang-Mi Park; Kiwon Han; Chan Woong Choi (Toxicon, 2025)

Eco-friendly utilization and microbiological characteristics of coal gangue substrate via functional microbial fermentation - Junhao Shi; Xiaoyu Zhang; Mengting Lu; Xingxing He; Yong Wan; Xuejing Yu; Zhiyong Huang; Minmin Cai; Chan Yu (Environmental Research, 2025)

The Roles of MYC2 Transcription Factor in JA-Signaling Pathway in Plants - Young-Hun Kim; Chan-Woo Park; Kwang Min Lee; Chang-Oh Hong; Hong-Joo Son; Keun Ki Kim; Hyeon Cheal Park; Yu-Jin Kim (Journal of Plant Biology, 2025)

First evidence of Gymnodimine D in Alexandrium ostenfeldii strain K-1354 - Jun-Geon Je; Nari Seo; Jaeseong Kim; Chan-Young Kim; Hye Won Kim; Jae Young Yu; You-Jin Jeon; Hyun Woo Kim; Yun Jo Chung; Hyun Joo An; Jung-Rae Rho; Young-Sang Kim (Algae, 2025)
This study presents a comprehensive analysis of gymnodimine-series toxins produced by Alexandrium ostenfeldii (K- 1354) using liquid chromatography tandem mass spectrometry (LC-MS/MS). Three peaks with identical precursor ions but different retention times were observed, suggesting the presence of isomers identified as gymnodimines B, C, and D. Employing an integrated approach combining LC-MS/MS with electron transfer dissociation, the study revealed the characteristic fragment ions of gymnodimine D. Notably, this study demonstrated the potential for isolating and purifying gymnodimine D from culturable A. ostenfeldii, addressing the current lack of commercially available standards for this isomer. This study contributes remarkably to marine biotoxin monitoring and the understanding of these structurally complex compounds.

A hybrid CNN-Transformer model for identification of wheat varieties and growth stages using high-throughput phenotyping - Yu-Jin Jeon; Min Jeong Hong; Chan Seop Ko; So Jin Park; Hyein Lee; Won-Gyeong Lee; Dae-Hyun Jung (Computers and Electronics in Agriculture, 2025)

Unveiling the role of aeration tanks in the emission and enrichment of airborne antibiotic resistance genes in a wastewater treatment plant - Jui-Hung Yen; Jun-Fa Yeh; Chih-Yu Chan; Hsin-Hsin Tung; Kai-Hsien Chi; Hsin-Chang Chen; Wan-Ru Chen; Charles C.-K. Chou; Ta-Chih Hsiao (Water Research, 2025)

Production and application of Paenibacillus polymyxa levan as an antiviral priming agent against cucumber mosaic virus infection in tobacco plants - Hyunjun Ko; Hangil Kim; Ji Won Heo; Sangjun Lee; Yongtae Yu; Hyebin Kim; Hyeon-Seok Oh; Chan-Gi Min; Seokmin Baek; Han Suk Choi; Sung Jin Moon; Woohyun Sim; et al. (Carbohydrate Polymers, 2025)

Pathway of typical β-Lactam antibiotics degradation by black soldier fly and response characteristic of its intestinal microbes - Fang Li; Chen Wang; Zhengzheng Zhao; Chongrui Yang; Bingqi Gao; Ziniu Yu; Jibin Zhang; Minmin Cai; Chan Yu (Bioresource Technology, 2025)

Enhancing percutaneous coronary intervention using TriVOCTNet: a multi-task deep learning model for comprehensive intravascular optical coherence tomography analysis - Yu Shi Lau; Li Kuo Tan; Kok Han Chee; Chow Khuen Chan; Yih Miin Liew (Physical and Engineering Sciences in Medicine, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Effect of cold acclimation on the supercooling point and cold hardiness substances in Heterolocha jinyinhuaphaga (Lepidoptera: Geometridae) - Yu-Yong Xiang; Chan Shi; Mao-Zhu Zhou (International Journal of Tropical Insect Science, 2025)

Intra-urban comparison of hazardous VOCs in Hong Kong: Source apportionment and integrated risk assessment - Xiangyunong Cao; Dasa Gu; Hao Sun; Ka Fung Leung; Yuchen Mai; Xin Li; Wai Ming Chan; Sin Ka Mak; Zhenxing Liang; Wentai Zhang; Yisheng Zhang; Shan Huang; et al. (Sustainable Cities and Society, 2025)

Association between air temperature exposure and childhood rhinitis risk, and the mediating role of ambient O3: A multi-city study of 40,103 Chinese preschool children - Zhiping Niu; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Jing Wei; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Influence of pipeline structure on flow pattern classification and void fraction in offshore riser systems - Yeqi Cao; Qiang Xu; Chan Wang; Haiyang Yu; Liejin Guo (Ocean Engineering, 2025)

Thermodynamic analysis of the effect of palm stearin on fully hydrogenated soybean oil coatings in granular micronutrient premixes - Y.K. Kiki Chan; Fletcher Han; Yu-Ling Cheng; Levente L. Diosady (Food Chemistry, 2025)

Characteristics and biological mechanism of protein degradation by the black solider fly (Hermetia illucens L.) larvae gut strain Bacillus subtilis S4 - Bingqi Gao; Yue Ao; Zhengzheng Zhao; Zhicheng Wang; Chongrui Yang; Minmin Cai; Chan Yu (Food Chemistry, 2025)

Gallibacterium faecale sp. nov., Isolated from Dairy Cow Feces - Seoung Woo Ryu; Jeong Chan Moon; Byeong Seob Oh; Seung Yeob Yu; Jeong Eun Bak; Eun Seo Heo; Seung-Hwan Park; Se Won Kang; Jiyoung Lee; Mi-Kyung Lee; Mooyoung Jung; Yo Han Choi; et al. (Current Microbiology, 2025)

Imagine, Discover, Inspire: Proceedings of the 4th International Conference of the Trisomy 21 Research Society - Lisi Flores-Aguilar; Eric D. Hamlett; Paula Araya; Eugenio Barone; Anita Bhattacharyya; Maria Carmona-Iragui; Li Chan; Brad Christian; Alberto C. S. Costa; Floriana Costanzo; Laura Del Hoyo Soriano; Mara Dierssen; et al. (NeuroMolecular Medicine, 2025)
Down syndrome (DS) or trisomy 21 (T21) is present in a significant number of children and adults around the world and is associated with cognitive and medical challenges. Through research, the T21 Research Society (T21RS), established in 2014, unites a worldwide community dedicated to understanding the impact of T21 on biological systems and improving the quality of life of people with DS across the lifespan. T21RS hosts an international conference every two years to support collaboration, dissemination, and information sharing for this goal. In 2022, T21RS hosted an international conference in Long Beach, California, from June 9 to 12. The conference, attended by 483 people including scientists, families, self-advocates, and industry representatives from 17 countries, was a dynamic and interactive meeting that shared discoveries from international research teams. This summary highlights the scientific discoveries shared at the 4th T21RS meeting with the Imagine, Discover, Inspire theme.

Exposure to outdoor humid-heat and indoor dampness-mold during infancy is associated with increased childhood asthma risk: A large-scale multi-city study in Chinese preschool children - Zhiping Niu; TianYi Chen; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Increased health risk from co-exposure to polycyclic aromatic hydrocarbons, phthalates, and per- and polyfluoroalkyl substances: Epidemiological insight from e-waste workers in Hong Kong - Junye Bian; Zhihui Guo; Gengze Liao; Feng Wang; Yanny Hoi Kuen Yu; Victoria H. Arrandale; Alan Hoi-shou Chan; Jiayin Huang; Yiming Ge; Xinjie Li; Xulong Chen; Bingjun Lu; et al. (Science of The Total Environment, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Coastal marine heatwaves in the Santa Barbara Channel: decadal trends and ecological implications - Kit Yu Karen Chan; Li Kui; Adriane M. McDonald; Amelia L. Ritger; Gretchen E. Hofmann (Frontiers in Marine Science, 2024)
Marine heatwaves (MHWs) are of increasing concern due to the emerging ecological and socioeconomic impacts on coastal ecosystems. Leveraging the data of the Santa Barbara Coastal Long-Term Ecological Research project, we analyzed the MHW event metrics observed in the kelp forest ecosystem and across Santa Barbara Channel, CA, USA. Not only was there a significant positive trend in the number of MHWs recorded, their duration and intensity were also increasing over time. MHWs were detected year-round, suggesting that marine organisms have exposure risks regardless of their phenology. Exposure at one life history stage could have a legacy effect on the subsequent stages, implying little temporal refuge. In contrast, the coastal mooring data revealed that near-surface and bottom events were not necessarily coupled even at less than 15 m. Such spatial variation in MHWs might provide a temporary refuge for mobile species. These observations also highlight the importance of depth-stratified, long-term coastal monitoring to understand spatio-temporal variation in MHW stress on coastal communities.

Bifunctional MOFs Nanozyme with Peroxidase Activity and Stimulus-responsive Fluorescent for Determination of Glyphosate - Yu-Meng Guo; Zi-Chong Chen; Kai-Xiang Zhang; Liu-Lu Liu; Chan Huang; Qing Li (Journal of Fluorescence, 2024)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

The de-structuration of eating models in East Asia under compressed food modernity: An empirical synthesis - Haruka Ueda; Yu-Chan Chiu (Appetite, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Predictive biomarkers for embryotoxicity: a machine learning approach to mitigating multicollinearity in RNA-Seq - Yixian Quah; Soontag Jung; Jireh Yi-Le Chan; Onju Ham; Ji-Seong Jeong; Sangyun Kim; Woojin Kim; Seung-Chun Park; Seung-Jin Lee; Wook-Joon Yu (Archives of Toxicology, 2024)

Brucella rough RB51 infection activates P53-Slc7a11-Gpx4/GSH pathway to induce ferroptosis to attenuate the intracellular survival on macrophages - Hai Hu; Guangdong Zhang; Mingxing Tian; Yi Yin; Yanqing Bao; Xiang Guan; Chan Ding; Shengqing Yu (Veterinary Microbiology, 2024)

Sensitivity analysis of building material, ground material, and tree parameters in microclimate simulations - Anh-Vu Le; Oi-Man Hip; Shun-Yu Yang; Ying-Chieh Chan (Urban Climate, 2024)

Patternable and flexible thermoelectric generators based on Bi2Te3/silk fibroin composites for temperature sensing and wearable applications - Qiaohang Guo; Jing Guo; Jiahao Zhou; Wei Yu; Peidi Zhou; Kaihuai Yang; Chan Zheng; Shaofeng Zeng; Nengbin Hua; Minghua You; Mingcen Weng (Chemical Engineering Journal, 2024)

Unveiling the evolutionary dynamics of microRNA-targeted plant laccase genes - Rui-Rui He; Meng-Qi Lei; Yan-Zhao Feng; Jiao Xue; Yu-Chan Zhang; Yue-Qin Chen; Yang Yu (Science China Life Sciences, 2024)

Dually-amplified electrochemical aptasensor based on the self-linking AuPt nanoflowers for ultrasensitive determination of hemagglutinin - Qing-Cai Yu; Yan Wang; Yao Liu; Chan-Ru Xiong; Xing Chen (Analytica Chimica Acta, 2024)

Rapid quantitative high-throughput mouse embryoid body model for embryotoxicity assessment - Yixian Quah; Soontag Jung; Onju Ham; Ji-Seong Jeong; Sangyun Kim; Woojin Kim; Jireh Yi-Le Chan; Seung-Chun Park; Seung-Jin Lee; Wook-Joon Yu (Archives of Toxicology, 2024)

Theoretical investigation on the oxidation mechanism of methylglyoxal in the aqueous phase - Yu Zhang; Ruifeng Zhang; Chak K. Chan; Maoxia He; Bo Wei; Huaqing Liu (Chemosphere, 2024)

Prediction of parameters in the Ibarra–Medina–Krawinkler model for reinforced concrete columns using random forest and active learning - Peng-Yu Chen; Kun-Chan Lee; Tsung-Lin Li (Soil Dynamics and Earthquake Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cyclic RGD conjugated PEG-PLGA nanoparticle enhances preventative effect of bilirubin on the development of ultraviolet-B (UVB)-induced cataract - Haiying Jin; Yang Huang; Yu Jin; Lijun Wang; Feiyue Xiao; Feng Qian; Chan Zhao (Chemical Engineering Journal, 2024)

Bactofencin YH, a novel bacteriocin with high inhibitory activity against clinical Streptococcus species - Hui-chung Wu; Jiro Arima; Chang-Hui Kuan; Yu-Chen Tsai; Yun-Shien Lee; Chin-Kan Chan; Yi-sheng Chen (World Journal of Microbiology and Biotechnology, 2024)

Pollen-Expressed Plant U-Box Protein, OsPUB14 Involves in Rice Fertility and Degrades OsMTD2 - Eun Young Kim; Sang Dae Yun; Myung-Hee Kim; Ji-Hyun Kim; Sung-Aeong Oh; Jung Hyun Lee; Ye-Jin Son; Woo-Jong Hong; Chan Mi Yun; Sunok Moon; Ki-Hong Jung; Yu-Jin Kim; et al. (Journal of Plant Biology, 2024)

Construction of dual Z-scheme Ag3VO4–BiVO4/InVO4 photocatalysts using vanadium source from spent catalysts for contaminated water treatment and bacterial inactivation - Kuen-Chan Lee; Shih-Chieh Hsu; Jen-Hsien Huang; Kuan-Syun Wang; Wei Kong Pang; Chih-Wei Hu; Yi-Jhen Jiang; Er-Chieh Cho; Huei Chu Weng; Ting-Yu Liu (Chemosphere, 2024)

A suspect screening strategy with automated data processing tools for the comprehensive detection of emerging chemical hazards in food - Hui Yi Lim; Dingyi Yu; Sheot Harn Chan; Angela Li (Food Control, 2024)

Polyphenol (−)-Epigallocatechin Gallate (EGCG) mitigated kidney injury by regulating metabolic homeostasis and mitochondrial dynamics involvement with Drp1-mediated mitochondrial fission in mice - Yue-Lei Chu; Jin-Chan Pi; Yu-Fei Yao; Xuan-Ying Chen; Xiao-Ping Peng; Wen-Juan Li (Food and Chemical Toxicology, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

The eating model in contemporary Taiwan: Destructuration or a new insight into compressed food modernity in Asia - Haruka Ueda; Yu-Chan Chiu (Appetite, 2024)

Genotoxicity and cytotoxicity in male reproductive cells caused by sediment pollutants - Meng-Wei Lin; Jai-Yu Chen; Yu-Xuan Ye; Wei-Yi Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Science of The Total Environment, 2024)

Prenatal and postnatal early life exposure to greenness and particulate matter of different size fractions in relation to childhood rhinitis - A multi-center study in China - Liu Yang; Han Chen; Huiyu Gao; Ying Wang; Tianyi Chen; Magnus Svartengren; Dan Norbäck; Jing Wei; Xiaohong Zheng; Ling Zhang; Chan Lu; Wei Yu; et al. (Science of The Total Environment, 2024)

Comprehensive identification of pathogenic microbes and antimicrobial resistance genes in food products using nanopore sequencing-based metagenomics - Annie Wing-Tung Lee; Iain Chi-Fung Ng; Evelyn Yin-Kwan Wong; Ivan Tak-Fai Wong; Rebecca Po-Po Sze; Kit-Yu Chan; Tsz-Yan So; Zhipeng Zhang; Sharon Ka-Yee Fung; Sally Choi-Ying Wong; Wing-Yin Tam; Hiu-Yin Lao; et al. (Food Microbiology, 2024)

Isochlorogenic acid A ameliorated lead-induced anxiety-like behaviors in mice by inhibiting ferroptosis-mediated neuroinflammation via the BDNF/Nrf2/GPX4 pathways - Jun-Tao Guo; Han-Yu Li; Chao Cheng; Jia-Xue Shi; Hai-Nan Ruan; Jun Li; Chan-Min Liu (Food and Chemical Toxicology, 2024)

Microalga Chlorella sp. biomass containing high lutein prevents light-induced photooxidation and retinal degeneration in mice - Hwa Young Yu; Dae-Hyun Cho; Daebang Seo; Chan Yoo; Su-Bin Park; Woo Kwon Jung; Jae Eun Jung; Hee-Sik Kim; Junghyun Kim (Algal Research, 2024)

Estimated daily intake and cumulative risk assessment of organophosphate esters and associations with DNA damage among e-waste workers in Hong Kong - Gengze Liao; Xueqiong Weng; Feng Wang; Yanny Hoi Kuen Yu; Victoria H. Arrandale; Alan Hoi-shou Chan; Shaoyou Lu; Lap Ah Tse (Chemosphere, 2024)

Hyaluronic acid-based injectable formulation developed to mitigate metastasis and radiation-induced skin fibrosis in breast cancer treatment - Yu-Chi Wang; Pei-Wei Shueng; Chan-Yu Hu; Fu-I Tung; Ming-Hong Chen; Tse-Ying Liu (Carbohydrate Polymers, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Greenness and its composition and configuration in association with allergic rhinitis in preschool children - Han Chen; Xia Meng; Yongfu Yu; Jin Sun; Zhiping Niu; Jing Wei; Ling Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Dan Norbäck; et al. (Environmental Research, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

Effects of transport densities on the physiological and biochemical characteristics of sturgeon (Acipenser baerii ♀ × A. schrenckii ♂) - Chan Bai; Zhaoding Wang; Jigui Yu; Juguang Wang; Liang Qiu; Yi Chai; Wei Cai; Guangquan Xiong; Tao Liao (Aquaculture, 2024)

Observational evidence for dynamic effect of cropland form on ozone in China - Zemin Xiao; Li Yu; Yonglin Shen; Ka Lok Chan; Ling Yao; Chenghu Zhou (Urban Climate, 2024)

Almond defect and freshness inspection system using hyperspectral imaging and deep learning techniques - Shih-Yu Chen; Mei-Yun Wang; Yung-Ming Kuo; Yu-Chia Chan; Yi-Cheng Chen (Postharvest Biology and Technology, 2024)

Integrating high-throughput phenotypic profiling and transcriptomic analyses to predict the hepatosteatosis effects induced by per- and polyfluoroalkyl substances - Yu-Syuan Luo; Ren-Yan Ying; Xsuan-Ting Chen; Yu-Jia Yeh; Chia-Cheng Wei; Chang-Chuan Chan (Journal of Hazardous Materials, 2024)

Coupling of gene regulation and carrier modification manipulates bacterial biofilms as robust living catalysts - Cheng-Hai Yan; Yu-Fan Zhan; Huan Chen; Richard A. Herman; Yan Xu; Marriam Khurshid; Lu-Chan Gong; Shuai You; Jun Wang (Bioresource Technology, 2024)

Pollution levels and ecological risks of PPCPs in water and sediment samples of Danjiangkou Reservoir - Haiyang Jin; Chan Yu; Li Lin; Jinghua Cheng; He Qin; Jingxiang Tao; Shengfei Deng (Environmental Science and Pollution Research, 2024)

Comparative analysis of Deinagkistrodon acutus venom from Taiwan and China utilizing chromatographic, electrophoretic, and bioinformatic approaches, along with ELISA employing a monospecific antivenom - Tein-Shun Tsai; Inn-Ho Tsai; Jing-Lin Qiu; Yuen-Ying Chan; Yu-Wei Chiang (Toxicon, 2024)

Associations between community green view index and fine particulate matter from Airboxes - Jia-Hong Tang; Ying-Jhen Huang; Ping-Hsien Lee; Yu-Ting Lee; Yu-Chun Wang; Ta-Chien Chan (Science of The Total Environment, 2024)

Intrauterine and early postnatal exposures to submicron particulate matter and childhood allergic rhinitis: A multicity cross-sectional study in China - Yachen Li; Lifeng Zhu; Jing Wei; Chuansha Wu; Zhuohui Zhao; Dan Norbäck; Xin Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Ling Zhang; et al. (Environmental Research, 2024)

Cruise observation of ambient volatile organic compounds over Hong Kong coastal water - Hao Sun; Dasa Gu; Xin Feng; Zhe Wang; Xiangyunong Cao; Mingyao Sun; Zhi Ning; Penggang Zheng; Yuchen Mai; Zijie Xu; Wai Ming Chan; Xin Li; et al. (Atmospheric Environment, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

Streptococcus taonis sp. nov., a novel bacterial species isolated from a blood culture of a patient - Chien-Yu Lee; Chin-Kan Chan; Momoko Chida; Mika Miyashita; Yun-Shien Lee; Hui-Chung Wu; Yu-Chung Chang; Wen-Ting Lin; Yi-Sheng Chen (Archives of Microbiology, 2024)

Microbiological Analysis of Manufacturing Processes and Microbial Hazard Assessment of Quality and Safety of Commercial Salted Shrimp (Saeu-jeot) - Jiyoun Jeong; Heeyoung Lee; Hwan Hee Yu; Jong-Chan Kim; Sunhyun Park; You-Shin Shim (Fishes, 2024)
The objective of this study was to evaluate the microbiological properties of commercially available traditional Korean salted shrimp (Saeu-jeot) and to analyze the effects of saltwater immersion and ultraviolet (UV) irradiation on the reduction of Staphylococcus aureus in Saeu-jeot. A microbiological analysis was conducted across 56 commercially available Saeu-jeot samples from the Korean, Chinese, and Vietnamese markets. The microbiological analysis revealed no presence of Escherichia coli, coliforms, or Vibrio parahaemolyticus in any commercial samples. The total viable count and S. aureus were 3.8 ± 0.4 and 0.6 ± 0.3 log CFU/g, respectively. An investigation of the procedures conducted on Saeu-jeot samples at various production stages by Hazard Analysis Critical Control Point (HACCP)-certified companies demonstrated the substantial relevance of the raw material (tiny shrimp) on S. aureus counts. In order to reduce S. aureus in Saeu-jeot, saltwater immersion and UV irradiation treatments were applied, which reduced the S. aureus counts by 1.4 log CFU/g and 0.3 log CFU/g, respectively, and S. aureus’s efficacy was limited to the food’s surface. These results suggest that a co-treatment of saltwater immersion and UV irradiation could be effective in reducing S. aureus. The maintenance of hygienic handling and cleanliness are essential in the modern manufacturing processes of Saeu-jeot.

Effects of personal noise exposure, sleep quality, and burnout on quality of life: An online participation cohort study in Taiwan - Ta-Chien Chan; Bing-Sheng Wu; Yu-Ting Lee; Ping-Hsien Lee (Science of The Total Environment, 2024)

Two-dimensional heterojunction layered graphene oxide/graphitic carbon nitride photocatalyst for removal of toxic environmental dye methylene blue - Homg-Ming Su; Dhanapal Vasu; Shang-Yu Chan; Yung-Chieh Liu; Jiaxin Jiang; Yu-Feng You; Te-Wei Chiu; Sheng-Chi Chen (Environmental Pollution, 2024)

Long-term impacts of endocrine-disrupting chemicals exposure on kidney function: A community-based cohort study - Chun-Yu Chen; Chin-Chan Lee; Heng-Jung Hsu; I-Wen Wu; Yung-Chang Chen; Heng-Chih Pan; Yih-Ting Chen; Cheng-Kai Hsu; Chiao-Yin Sun (Environmental Toxicology and Pharmacology, 2024)

TALE-based organellar genome editing and gene expression in plants - Jer-Young Lin; Yu-Chang Liu; Yan-Hao Tseng; Ming-Tsair Chan; Ching-Chun Chang (Plant Cell Reports, 2024)

Technical, commercial, and regulatory challenges of cellular agriculture for seafood production - Dorothy Leung-Kwan Chan; Pei-Yu Lim; Arleen Sanny; Danai Georgiadou; Alison P. Lee; Andy Hee-Meng Tan (Trends in Food Science & Technology, 2024)

Estimating annual CO2 emissions and building a leakage scenario in a tectonically quiescent area - Soonyoung Yu; Gitak Chae; Sung-Wook Kim; Ho-Rim Kim; Chan Yeong Kim; Gibeom Seok; Seong-Taek Yun (Journal of Geochemical Exploration, 2024)

Rice husk hydrochar prepared by hydrochloric acid assisted hydrothermal carbonization for levofloxacin removal in bioretention columns - Yidan Luo; Yuanwang Lan; Shuzhen Liang; Shuohan Yu; Mingshan Xue; Zuozhu Yin; Fang-Fang Shen; Xibao Li; Zhen Hong; Meiling Yan; Chan Xie; Bin Gao (Bioresource Technology, 2024)

Early-life long-term ibuprofen exposure reduces reproductive capacity involved in spermatogenesis impairment and associated with the transcription factor DAF-5 in Caenorhabditis elegans - Chan-Wei Yu; Pei-Ling Yen; Chun Ming How; Yu-Hsuan Kuo; Vivian Hsiu-Chuan Liao (Chemosphere, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

The impact of rice-crayfish field on socio-ecological system in traditional farming areas: Implications for sustainable agricultural landscape transformation - Youlin Chen; Peiheng Yu; Lei Wang; Yiyun Chen; Edwin Hon Wan Chan (Journal of Cleaner Production, 2024)

Tailored bacteria tackling with environmental mercury: Inspired by natural mercuric detoxification operons - Chang-ye Hui; Bing-chan Ma; Shun-yu Hu; Can Wu (Environmental Pollution, 2024)

Home environment exposure and sick building syndrome (SBS) symptoms among adults in southern China: Health associations in 2010 and 2019 - Hong Cheng; Dan Norbäck; Huilin Zhang; Liu Yang; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; et al. (Building and Environment, 2024)

A predictive model incorporating geomorphic factors for assessing the longevity of landslide-dammed lakes - Shao-Wei Wu; Wan-Yu Chan; Chao-Yuan Lin (Landslides, 2024)

Anti-obesity activity of human gut microbiota Bacteroides stercoris KGMB02265 - Seoung Woo Ryu; Jeong Chan Moon; Byeong Seob Oh; Seung Yeob Yu; Jeong Eun Bak; Eun Seo Heo; Jae-Ho Jeong; Ju Huck Lee (Archives of Microbiology, 2024)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

Prediction and optimization of frying conditions of air fried pork rind using a direct linking model - Der-Sheng Chan; Hong-Ting Victor Lin; Yu-Hsiang Huang; Yu-Jin Syu; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2023)

Velocity distribution and movement of multiple slow-moving landslides characterized by an optimized MTInSAR workflow - Chiao-Yin Lu; Yu-Chang Chan; Jyr-Ching Hu; Chun-Ying Chiu; Chung-Ray Chu; Chia-Han Tseng; Chih-Hsin Chang (Engineering Geology, 2023)

Characterization of toxic air pollutants in Hong Kong, China: Two-decadal trends and health risk assessments - Yee Ka Wong; Wai Wai Chan; Dasa Gu; Tze Wai Wong; Keith Jin Deng Chan; Jian Zhen Yu; Alexis Kai Hon Lau (Atmospheric Environment, 2023)

Proliferation-Related Features of the Human Mesenchymal Stem Cells Derived from Palatine Tonsils, Adipose Tissues, and Bone Marrow - Sohee Park; Yeuni Yu; Gi Cheol Park; Sung-Chan Shin; Ji Min Kim; Byung-Joo Lee; Yun Hak Kim (Tissue Engineering and Regenerative Medicine, 2023)

Simulation of passive exotendon assistive device for agricultural harvesting task - Yon Sin Chan; Yu Xuan Teo; Darwin Gouwanda; Surya Girinatha Nurzaman; Alpha Agape Gopalai (Physical and Engineering Sciences in Medicine, 2023)
This study proposes and investigates the feasibility of the passive assistive device to assist agricultural harvesting task and reduce the Musculoskeletal Disorder (MSD) risk of harvesters using computational musculoskeletal modelling and simulations. Several passive assistive devices comprised of elastic exotendon, which acts in parallel with different back muscles (rectus abdominis, longissimus, and iliocostalis), were designed and modelled. These passive assistive devices were integrated individually into the musculoskeletal model to provide passive support for the harvesting task. The muscle activation, muscle force, and joint moment were computed with biomechanical simulations for unassisted and assisted motions. The simulation results demonstrated that passive assistive devices reduced muscle activation, muscle force, and joint moment, particularly when the devices were attached to the iliocostalis and rectus abdominis. It was also discovered that assisting the longissimus muscle can alleviate the workload by distributing a portion of it to the rectus abdominis. The findings in this study support the feasibility of adopting passive assistive devices to reduce the MSD risk of the harvesters during agricultural harvesting. These findings can provide valuable insights to the engineers and designers of physical assistive devices on which muscle(s) to assist during agricultural harvesting.

Intermodal comparison of commuters’ exposure to VOCs between public, private, and active transportation - Hsi-Hsien Yang; Narayan Babu Dhital; Yi Hsuan Lai; Tsai Yu Chan (Environmental Monitoring and Assessment, 2023)

Screening of Peptides that Specifically Binds to M3-M4 Extracellular Domain of Sodium Pump α1 Subunit and Analysis of Their Bioactivity In Vitro and In Vivo - Tianjiao Wen; Chan Li; Siying Li; Peipei Yu; Xiaoran Yu; Luya Li; Jingxia Cui (Bulletin of Experimental Biology and Medicine, 2023)

Parentage influence on gene expression under acidification revealed through single‐embryo sequencing - Cheuk Wang Fung; Kin Yung Chau; Daniel Chun Sang Tong; Claire Knox; Sindy Sing Ting Tam; Sin Yen Tan; Danson Shek Chun Loi; Ziuwin Leung; Ying Xu; Yi Lan; Pei‐Yuan Qian; Kit Yu Karen Chan; et al. (Molecular Ecology, 2023)
The dissolution of anthropogenic carbon dioxide (CO 2 ) in seawater has altered its carbonate chemistry in the process of ocean acidification (OA). OA affects the viability of marine species. In particular, calcifying organisms and their early planktonic larval stages are considered vulnerable. These organisms often utilize energy reserves for metabolism rather than growth and calcification as supported by bulk RNA‐sequencing (RNA‐seq) experiments. Yet, transcriptomic profiling of a bulk sample reflects the average gene expression of the population, neglecting the variations between individuals, which forms the basis for natural selection. Here, we used single‐embryo RNA‐seq on larval sea urchin Heliocidaris crassispina , which is a commercially and ecologically valuable species in East Asia, to document gene expression changes to OA at an individual and family level. Three paternal half‐sibs groups were fertilized and exposed to 3 pH conditions (ambient pH 8.0, 7.7 and 7.4) for 12 h prior to sequencing and oxygen consumption assay. The resulting transcriptomic profile of all embryos can be distinguished into four clusters, with differences in gene expressions that govern biomineralization, cell differentiation and patterning, as well as metabolism. While these responses were influenced by pH conditions, the male identities also had an effect. Specifically, a regression model and goodness of fit tests indicated a significant interaction between sire and pH on the probability of embryo membership in different clusters of gene expression. The single‐embryo RNA‐seq approach is promising in climate stressor research because not only does it highlight potential impacts before phenotypic changes were observed, but it also highlights variations between individuals and lineages, thus enabling a better determination of evolutionary potential.

Biofloc Application Using Aquaponics and Vertical Aquaculture Technology in Aquaculture: Review - Young-Bin Yu; Jae-Ho Choi; Ju-Hyeong Lee; A-Hyun Jo; Sung Won Han; Song-Hun Han; Hee Jae Choi; Cheol Young Choi; Ju-Chan Kang; EunYoung Min; Jun-Hwan Kim (Fishes, 2023)
Some aspects of traditional aquaculture have negative impacts on the aquatic environment, leading to pollution and disease outbreaks in farmed organisms. Biofloc technology (BFT) is a closed aquaculture system that utilizes specific microbial communities to remove ammonia emitted from aquaculture organisms or adds carbon to the aquaculture system to improve water quality. BFT has benefits, such as increasing production and improving water quality, and reducing disease spread and pollution, without the need for water exchange. However, there are disadvantages, such as rapid changes in water quality due to accumulation of dissolved nutrients and total suspended soils (TSS) and the requirement for expensive aeration equipment to maintain dissolved oxygen. BFT can be enhanced in value and efficiency by combining it with other aquaculture technologies, such as aquaponics and vertical aquaculture to overcome the disadvantages. The integration of biofloc with technologies from the fourth industrial revolution holds potential for further development, while aquaponics and vertical farming can eliminate geographical limitations and accelerate the urbanization of aquaculture. The integration of aquaponics and vertical aquaculture with BFT has potential for development, accelerating the urbanization of aquaculture and removing geographic limitations.

Particulate organic emissions from incense-burning smoke: Chemical compositions and emission characteristics - Kai Song; Rongzhi Tang; Ang Li; Zichao Wan; Yuan Zhang; Yuanzheng Gong; Daqi Lv; Sihua Lu; Yu Tan; Shuyuan Yan; Shichao Yan; Jingshun Zhang; et al. (Science of The Total Environment, 2023)

Corrigendum to “The application and future of biofloc technology (BFT) in aquaculture industry: A review” [342, 15 September 2023, 118237] - Young-Bin Yu; Ju-Hyeong Lee; Jae-Ho Choi; Young Jae Choi; A-Hyun Jo; Cheol Young Choi; Ju-Chan Kang; Jun-Hwan Kim (Journal of Environmental Management, 2023)

Cheaper radiative cooling paint by milling larger glass bubbles - Xinxian Yu; Hoi Fung Ronaldo Chan; Can Xiao; Chun Chen (Energy and Buildings, 2023)

Novel self-degradable prodrug blend thermogel for intratympanic drug delivery to treat inner ear diseases - Thi Phuc Le; Yang Yu; Hyuk Chan Kwon; Sun-Ae Shin; Yong-Ho Park; Kang Moo Huh (Chemical Engineering Journal, 2023)

Dampness and mould in Chinese homes and sick building syndrome (SBS) symptoms – Associations with climate, family size, cleaning and ventilation - Bin Zhang; Dan Norbäck; Hong Cheng; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; Tingting Wang; et al. (Building and Environment, 2023)

MOF-derived spinel NiMn2O4/CoMn2O4 heterojunction and its application in a high-performance photocatalyst and supercapacitor - Kuen-Chan Lee; Yu-Sheng Hsiao; Ming-Yen Sung; Yi-Lun Chen; Nian-Jheng Wu; Jen-Hsien Huang; Er-Chieh Cho; Huei Chu Weng; Shih-Chieh Hsu (Journal of Environmental Chemical Engineering, 2023)

Mechanisms underlying probiotic effects on neurotransmission and stress resilience in fish via transcriptomic profiling - Yoonhang Lee; Thanh Luan Nguyen; HyeongJin Roh; Ahran Kim; Jiyeon Park; Ju-Yeop Lee; Yu-Ra Kang; Hyoyeong Kang; Min-Young Sohn; Chan-Il Park; Do-Hyung Kim (Fish & Shellfish Immunology, 2023)

Linking hydrological connectivity to sustainable watershed management in the Loess Plateau of China - Yang Yu; Juanlong Feng; Hu Liu; Chuandong Wu; Jianjun Zhang; Zhengze Wang; Chan Liu; Jiongchang Zhao; Jesús Rodrigo-Comino (Current Opinion in Environmental Science & Health, 2023)

Novel MIL-88B(Fe)/ZnTi-LDH high-low junctions for adsorption and photodegradation of tetracycline: Characteristics, performance, and mechanisms - Yidan Luo; Guangying Shi; Shuohan Yu; Zitao Liu; Jiawei Yin; Mingshan Xue; Qing Sun; Fang-Fang Shen; Xibao Li; Zuozhu Yin; Chan Xie; Bin Gao (Chemical Engineering Journal, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

An integrated approach for examining urban fragmentation in metropolitan areas: Implications for sustainable urban planning - Peiheng Yu; Esther H.K. Yung; Edwin H.W. Chan; Man Sing Wong; Siqiang Wang; Yiyun Chen (Journal of Cleaner Production, 2023)

The application and future of biofloc technology (BFT) in aquaculture industry: A review - Young-Bin Yu; Ju-Hyeong Lee; Jae-Ho Choi; Young Jae Choi; A-Hyun Jo; Cheol Young Choi; Ju-Chan Kang; Jun-Hwan Kim (Journal of Environmental Management, 2023)

Open space fragmentation in Hong Kong's built–up area: An integrated approach based on spatial horizontal and vertical equity lenses - Peiheng Yu; Edwin H.W. Chan; Esther H.K. Yung; Man Sing Wong; Yiyun Chen (Environmental Impact Assessment Review, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Paper-based microﬂuidics and tailored gold nanoparticles for visual colorimetric detection of multiplex allergens - Yuxing Yang; Xiaofei Zeng; Chan Fu; Lingxiao Tan; Naidi Yang; Yongxin Liu; Qian Shen; Jifu Wei; Changmin Yu; Chen Lu (Analytica Chimica Acta, 2023)

Description of a new moray eel ( Anguilliformes: Muraenidae ) from the Philippines , with a preliminary assessment of genetic and morphological variations of the Uropterygius concolor species complex - Wen‐Chien Huang; Rodulf Anthony Balisco; Florence Chan Evacitas; Te‐Yu Liao (Journal of Fish Biology, 2023)
Uropterygius concolor Rüppell, the type species of the genus Uropterygius , is a small, uniformly brown moray considered to be widely distributed in the Indo‐Pacific region. However, a recent study indicated that the real U. concolor is currently known only from the type locality in the Red Sea, and species recorded outside the Red Sea may represent a species complex that comprises several species. In this study, we assess the genetic and morphological variations of this species complex based on available data. Analyses of cytochrome c oxidase subunit I sequences revealed at least six distinct genetic lineages recognized under ‘ U. concolor ’. After carefully comparing the morphologies, one of the lineages is described herein as a new species, Uropterygius mactanensis sp. nov., based on 21 specimens collected from Mactan Island, Cebu, Philippines. Another distinct lineage is considered to be a possibly undescribed species based on diagnostic morphological characters. Although the taxonomic status of junior synonyms of U. concolor and some lineages still remain unresolved, this study provides informative morphological characters ( i.e. , tail length, trunk length, vertebrae number, and arrangement of teeth) that can be used in future studies on this species complex.

Trajectory Tracking Design for Unmanned Surface Vessels: Robust Control Approach - Yung-Hsiang Chen; Ming-Zhen Ellis-Tiew; Yu-Hsiang Chan; Guan-Wun Lin; Yung-Yue Chen (Journal of Marine Science and Engineering, 2023)
We propose a robust nonlinear trajectory tracking design by integrating a nonlinear model transformation, robust disturbance eliminator, and trajectory generator for unmanned surface vessels influenced by modeling uncertainties and ocean environmental disturbances. We designed this nonlinear control law to help control unmanned surface vessels following any designated sail trajectory constructed by the trajectory generator. With cubic spline interpolation, this trajectory generator can generate arbitrary smooth trajectories. Simulation results show that the proposed nonlinear robust control law has precise trajectory tracking performance and a robustness property for unmanned surface vessels under harsh ocean environmental disturbances and modeling uncertainties.

Toxic effects of microplastic (polyethylene) exposure: Bioaccumulation, hematological parameters and antioxidant responses in crucian carp, Carassius carassius - Young-Bin Yu; Jae-Ho Choi; Cheol Young Choi; Ju-Chan Kang; Jun-Hwan Kim (Chemosphere, 2023)

Intercellular mitochondrial component transfer triggers ischemic cardiac fibrosis - Chan Zhang; Hao Hao; Yishi Wang; Nan Mu; Wenhua Jiang; Zihui Zhang; Yue Yin; Lu Yu; Alex Chia Yu Chang; Heng Ma (Science Bulletin, 2023)

Experimental performance of multi-layered membrane breakwaters - Yu Chan Guo; S.C. Mohapatra; C. Guedes Soares (Ocean Engineering, 2023)

Increased risk of respiratory and allergic diseases in preschoolers from building envelope dampness exposure: Repeated cross-sectional surveys in multicity China - Wei Yu; Yan Zhang; Baizhan Li; Yinping Zhang; Chenqiu Du; Zhuohui Zhao; Dan Norback; Jiao Cai; Qihong Deng; Chan Lu; Hua Qian; Xiaohong Zheng; et al. (Building and Environment, 2023)

An experimental study on the performance of combined membrane breakwaters against incident waves - Yu Chan Guo; S.C. Mohapatra; C. Guedes Soares (Ocean Engineering, 2023)

The 2022 summer marine heatwaves and coral bleaching in China's Greater Bay Area - Yu Zhao; Mingru Chen; Tzu Hao Chung; Leo Lai Chan; Jian-Wen Qiu (Marine Environmental Research, 2023)

Molecular mechanisms underlying the vulnerability of Pacific abalone (Haliotis discus hannai) to Vibrio harveyi infection at higher water temperature - Yoonhang Lee; HyeongJin Roh; Ahran Kim; Jiyeon Park; Ju-Yeop Lee; Yoon-Jae Kim; Yu-Ra Kang; Hyoyeong Kang; Suhkmann Kim; Heui-Soo Kim; Hee-Jae Cha; Yung Hyun Choi; et al. (Fish & Shellfish Immunology, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Mitigation of antibiotic resistome in swine manure by black soldier fly larval conversion combined with composting - Zhengzheng Zhao; Chan Yu; Chongrui Yang; Bingqi Gao; Núria Jiménez; Chen Wang; Fang Li; Yue Ao; Longyu Zheng; Feng Huang; Jeffery K. Tomberlin; Zhuqing Ren; et al. (Science of The Total Environment, 2023)

Nanoplastics exposure disrupts circadian rhythm associated with dysfunction of the endolysosomal pathway and autophagy in Caenorhabditis elegans - Chan-Wei Yu; Yi-Chun Wu; Vivian Hsiu-Chuan Liao (Journal of Hazardous Materials, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

Dietary docosahexaenoic acid reduces fat deposition and alleviates liver damage induced by D-galactosamine and lipopolysaccharides in Nile tilapia (Oreochromis niloticus) - Yi-Chan Liu; Samwel Mchele Limbu; Jin-Gang Wang; Mai Wang; Li-Qiao Chen; Fang Qiao; Yuan Luo; Mei-Ling Zhang; Zhen-Yu Du (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The male sterility of bread wheat line XN291S was resulted from the deletion of a large segment at the end of 6BS - Minghu Zhang; Jiazheng Yu; Qijun Xie; Shaozhe Wen; Jinghui Li; Chan Bi; Chaojie Xie; Zhongfu Ni; Rongqi Liang; Mingshan You (Euphytica, 2023)

Brain compartmentalization based on transcriptome analyses and its gene expression in Octopus minor - Chan-Jun Lee; Hae-Youn Lee; Yun-Sang Yu; Kyoung-Bin Ryu; Hyerim Lee; Kyunghwan Kim; Song Yub Shin; Young-Chun Gil; Sung-Jin Cho (Brain Structure and Function, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Protocol for efficient ginseng transformation - Young-Hun Kim; Chan-Woo Park; Woo-Jong Hong; Ick Hyun Jo; Keun Ki Kim; Yu-Jin Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Capturing open space fragmentation in high–density cities: Towards sustainable open space planning - Peiheng Yu; Esther H.K. Yung; Edwin H.W. Chan; Siqiang Wang; Youlin Chen; Yiyun Chen (Applied Geography, 2023)

Transition of carbon-nitrogen coupling under different anthropogenic disturbances in subtropical small mountainous rivers - Li-Chin Lee; Gabriele Weigelhofer; Thomas Hein; Shin-Chien Chan; Ying-San Liou; Chien-Sen Liao; Fuh-Kwo Shiah; Yu-Lin Yu; Tsung-Yu Lee; Jr-Chuan Huang (Science of The Total Environment, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

Highly active cobalt-free perovskites with Bi doping as bifunctional oxygen electrodes for solid oxide cells - Kyung Taek Bae; Incheol Jeong; Doyeub Kim; Hyeongmin Yu; Ha-Ni Im; Akhmadjonov Akromjon; Chan-Woo Lee; Kang Taek Lee (Chemical Engineering Journal, 2023)

Co-contaminants of ethinylestradiol and sulfamethoxazole in groundwater exacerbate ecotoxicity and ecological risk and compromise the energy budget of C. elegans - Yu-Hsuan Kuo; Chun Ming How; Chi-Wei Huang; Pei-Ling Yen; Chan-Wei Yu; Chun-Han Chang; Vivian Hsiu-Chuan Liao (Aquatic Toxicology, 2023)

Determining meteorologically-favorable zones for seasonal influenza activity in Hong Kong - Ka Chun Chong; Paul K. S. Chan; Tsz Cheung Lee; Steven Y. F. Lau; Peng Wu; Christopher K. C. Lai; Kitty S. C. Fung; Cindy W. S. Tse; Shuk Yu Leung; Ka Li Kwok; Conglu Li; Xiaoting Jiang; et al. (International Journal of Biometeorology, 2023)

The impact of temperature and precipitation on all-infectious-, bacterial-, and viral-diarrheal disease in Taiwan - Gerry Andhikaputra; Amir Sapkota; Yu-Kai Lin; Ta-Chien Chan; Chuansi Gao; Li-Wen Deng; Yu-Chun Wang (Science of The Total Environment, 2023)

Study on the Competitive Adsorption of Pb (II) and Ni (II) in Aqueous Solution Onto B-nZVI and Its Stability After Adsorption - Xiaoqing Cai; Yinxia Wu; Yu Chuang; Chan He; Tiantian Shi (Water, Air, & Soil Pollution, 2023)

Parabacteroides faecalis sp. nov. Isolated from Swine Faeces - Jeong Eun Bak; Byeong Seob Oh; Seoung Woo Ryu; Seung Yeob Yu; Won Jung Choi; Ji-Sun Kim; Jung-Sook Lee; Seung-Hwan Park; Se Won Kang; Jiyoung Lee; Mi-Kyung Lee; Chan Seok Yun; et al. (Current Microbiology, 2023)

Assessing the public-private partnership handover: Experience from China's water sector - Fengyu Bao; Igor Martek; Albert P.C. Chan; Chuan Chen; Yang Yang; Heng Yu (Utilities Policy, 2023)

Microplastic accelerate the phosphorus-related metabolism of bacteria to promote the decomposition of methylphosphonate to methane - Junhong Li; Chan Yu; Zeqin Liu; Yan Wang; Fei Wang (Science of The Total Environment, 2023)

Adsorption and photodegradation of reactive red 120 with nickel-iron-layered double hydroxide/biochar composites - Yidan Luo; Yonghu Wang; Feng Hua; Mingshan Xue; Xianchuan Xie; Yu Xie; Shuohan Yu; Longshuai Zhang; Zuozhu Yin; Chan Xie; Zhen Hong (Journal of Hazardous Materials, 2023)

Transformation mechanism of methylphosphonate to methane by Burkholderia sp: Insight from multi-labeled water isotope probing and transcriptomic - Junhong Li; Houquan Liu; Zeqin Liu; Xianhua Zhang; Ruth Elaine Blake; Zhiyong Huang; Minmin Cai; Fei Wang; Chan Yu (Environmental Research, 2023)

Integrated adsorption and photodegradation of tetracycline by bismuth oxycarbonate/biochar nanocomposites - Yidan Luo; Aofeng Zheng; Junda Li; Yu Han; Mingshan Xue; Longshuai Zhang; Zuozhu Yin; Chan Xie; Zhi Chen; Li Ji; Zhen Hong; Xianchuan Xie (Chemical Engineering Journal, 2023)

Interfacial coupled engineering of plasmonic amorphous MoO3-x nanodots/g-C3N4 nanosheets for photocatalytic water splitting and photothermal conversion - Yumei Ren; Desheng Feng; Zhiming Yan; Zixu Sun; Zixuan Zhang; Dongwei Xu; Chong Qiao; Zhonghui Chen; Yu Jia; Seong Chan Jun; Shude Liu; Yusuke Yamauchi (Chemical Engineering Journal, 2023)

Large presence of bromine and toxic metals in ambient fine particles from urban fires - Tao Li; Hanzhe Chen; Jimmy C.H. Fung; Damgy H.L. Chan; Alfred L.C. Yu; Kenneth K.M. Leung; Jian Zhen Yu (Atmospheric Environment, 2023)

Riemerella anatipestifer GldG is necessary for secretion of effectors by type IX secretion system - Zongchao Chen; Wenlong Han; Min Zhu; Dan Liu; Pengfei Niu; Ruyu Shen; Chan Ding; Shengqing Yu (Veterinary Microbiology, 2023)

CO2 dynamics in a small and old subtropical reservoir in East Asia: Environmental controls driving seasonal and spatial variability - Chun Ngai Chan; Matthew J. Bogard; Fong Ching Ma; Yu Ching Ip; Boyi Liu; Shuai Chen; Lishan Ran (Science of The Total Environment, 2023)

On the urban compactness to ecosystem services in a rapidly urbanising metropolitan area: Highlighting scale effects and spatial non–stationary - Peiheng Yu; Shujin Zhang; Esther H.K. Yung; Edwin H.W. Chan; Bo Luan; Yiyun Chen (Environmental Impact Assessment Review, 2023)

Exploring the Wenchuan earthquake fault through the accurate location of WFSD-4# Well using seismic reflection - Yang-Yang Feng; Chang-Qing Yu; Hai-Bing Li; Chen Qu; Chan Wu; Qi Wang; Su Luo; Jin-Peng Huang; Ghazi Rehana (Applied Geophysics, 2022)

Trimethylamine N-oxide facilitates the progression of atrial fibrillation in rats with type 2 diabetes by aggravating cardiac inflammation and connexin remodeling - Wan-Ying Jiang; Jun-Yu Huo; Sheng-Chan Wang; Yan-Di Cheng; Yi-Ting Lyu; Zhi-Xin Jiang; Qi-Jun Shan (Journal of Physiology and Biochemistry, 2022)

SOX11-dependent CATSPER1 expression controls colon cancer cell growth through regulation the PI3K/AKT signaling pathway - Yang Huang; Yicheng Wang; Zhongmei Wu; Tao Li; Shupei Li; Chan Wang; Jine Ao; Changming Yang; Yu Zhou (Genes & Genomics, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Antifungal and Antibiofilm In Vitro Activities of Ursolic Acid on Cryptococcus neoformans - Wen-Jing Wang; Chan-Chan Liu; Yan-Tong Li; Miao-Qian Li; Yu-Ting Fu; Xin-Chen Li; Jie-Kang; Wei-Dong Qian (Current Microbiology, 2022)

Genome of elegance coral Catalaphyllia jardinei (Euphylliidae) - Yifei Yu; Wenyan Nong; Wai Lok So; Yichun Xie; Ho Yin Yip; Jasmine Haimovitz; Thomas Swale; David M. Baker; William G. Bendena; Ting Fung Chan; Apple P. Y. Chui; Kwok Fai Lau; et al. (Frontiers in Marine Science, 2022)
Coral reefs are under stress throughout the world. To better understand the molecular mechanisms underlying coral biology and their genomic evolution, here we sequenced the genome and transcriptomes of elegance coral Catalaphyllia jardinei (Euphylliidae). This monotypic genus stony coral is widespread but rare, being found across the Indo-West Pacific, from the northern Indian Ocean, Australia, Philippines, to the South China Sea. Due to its popularity among aquarium hobbyists, it is an overexploited species collected in large quantities from the wild for aquarium trade. The assembled genome is ~ 651.3 Mb in total length and of high physical contiguity with a scaffold N50 size of 28.9 Mb. The gene copy numbers of abiotic stress regulator (heat shock protein family genes) and neuropeptides (GLWamide, GRFamide, PRGamide and HIRamide) are similar to other sequenced anthozoans, and we have also identified the first set of sesquiterpenoid biosynthetic pathway genes in coral. Sequencing of small RNAs allows us to identify 35 microRNAs in C. jardinei and update the number of conserved microRNAs in cnidarians. This study established a foundation for further investigation into the roles of sesquiterpenoids and microRNAs in development of coral and understand their responses to climate change. Due to the easiness to culture C. jardinei in reef tanks and the established resources in this study, we propose this species be adopted as a new laboratory model in environmental and ecological experiments aiming to understand coral biology and responses to environmental stressors.

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Electroporation-Based CRISPR/Cas9 Mosaic Mutagenesis of β-Tubulin in the Cultured Oyster - Jiulin Chan; Wei Zhang; Yue Xu; Yu Xue; Linlin Zhang (Frontiers in Marine Science, 2022)
Genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 is enabling genetics improvement of productive traits in aquaculture. Previous studies have proven CRISPR/Cas9 to be feasible in oyster, one of the most cultured shellfish species. Here, we applied electroporation-based CRISPR/Cas9 knockout of β-tubulin and built a highly efficient genome editing system in Crassostrea gigas angulate . We identified the β-tubulin gene in the oyster genome and showed its spatiotemporal expression patterns by analyzing RNA-seq data and larval in situ hybridization. We further designed multiple highly specific guide RNAs (sgRNAs) for its coding sequences. Long fragment deletions were detected in the mutants by agarose gel electrophoresis screening and further verified by Sanger sequencing. In addition, the expression patterns of Cgβ-tubulin in the trochophore peritroch and intestinal cilia cells were altered in the mutants. Scanning electron microscopy represented shortened and almost complete depleted cilia at the positions of peritroch and the posterior cilium ring in Cgβ-tubulin mosaic knockout trochophores. Moreover, the larval swimming behavior in the mutants was detected to be significantly decreased by motility assay. These results demonstrate that β-tubulin is sufficient to mediate cilia development and swimming behavior in oyster larvae. By applying Cgβ-tubulin as a marker gene, our study established CRISPR/Cas9-mediated mosaic mutagenesis technology based on electroporation, providing an efficient tool for gene function validation in the oyster. Moreover, our research also set up an example that can be used in genetic engineering breeding and productive traits improvement in oysters and other aquaculture species.

Alternative Splicing of the Lobster (Homarus americanus) Crustacean Hyperglycemic Hormone A and B Genes Produce 2 Protein Variants Involved in Vitellogenin Inhibition - Cheng Gui Wang; Wei Wang; Li Li Shi; Yu Chun Shen; Siuming F. Chan (Frontiers in Marine Science, 2022)
Current BLASTP search analysis results suggested that the lobster ( Homarus americanus ) HaCHH-A and HaCHH-B may be derived from two different four-exon genes. Repeated tissue expression studies have revealed much different expression patterns of these two genes from those reported in the past. With RT-PCR, rapid amplification of complementary DNA (cDNA) ends (RACE), and genomic DNA cloning, we confirmed that the HaCHH-A and HaCHH-B transcripts were derived from two different four-exon CHH genes. By an alternative splicing mechanism, each gene can produce different but larger transcript variants (i.e., sHaCHH-A and sHaCHH-B ) mainly in different non-eyestalk tissues of the females. The larger and unspliced transcripts can be detected in the hepatopancreas, gill, heart, nerve cord, brain, ovary, and thoracic ganglion of the reproductive females. The expression patterns of sHaCHH-A and sHaCHH-B in other non-eyestalk tissues suggest that these transcripts have a wide spectrum of expressions during the female reproductive cycle. An in vitro organ explant culture system was developed to investigate the reproductive function of these cDNAs. The results showed that the recombinant proteins for sHaCHH-A and sHaCHH-B inhibited the gene expression of vitellogenin, whereas the double-stranded RNA (dsRNA) for sHaCHH-A and sHaCHH-B stimulated the expression of the vitellogenin gene in vitro . The results of the study may provide insights for the development of techniques to induce gonad development without using eyestalk ablation operation. This is the first in-depth report of the characterization of two four-exon CHH genes in a crustacean.

Jageum-Jung, the herbal pharmaceuticals, inhibits the hepatic fibrogenesis as mediated with TGF-β1/smad signaling - Yu Rim Song; Mi Hee Jang; Boyun Jang; Su Jin Bae; Seon Been Bak; Sung Min Lee; Un-Jung Yun; Ju Hee Lee; Sang Mi Park; Dae Hwa Jung; Bok Suk Sa; Jong Kuk Song; et al. (Molecular & Cellular Toxicology, 2022)

Spatially-explicit quantitative relationship for a potential PES mechanism: Cascade hydropower development in Yarlung Zangbo River Basin, China - Xiao-kang Zhu; Bin Fu; Ramon Felipe Bicudo Da Silva; Ying-man Guo; Chan-yuan Qin; Ting Feng; Hai-bing Yu; Kuang Xiao (Journal of Mountain Science, 2022)

Chronic mild stress paradigm as a rat model of depression: facts, artifacts, and future perspectives - Tatyana Strekalova; Yanzhi Liu; Daniel Kiselev; Sharafuddin Khairuddin; Jennifer Lok Yu Chiu; Justin Lam; Ying-Shing Chan; Dmitrii Pavlov; Andrey Proshin; Klaus-Peter Lesch; Daniel C. Anthony; Lee Wei Lim (Psychopharmacology, 2022)
Rationale The chronic mild stress (CMS) paradigm was first described almost 40 years ago and has become a widely used model in the search for antidepressant drugs for major depression disorder (MDD). It has resulted in the publication of almost 1700 studies in rats alone. Under the original CMS procedure, the expression of an anhedonic response, a key symptom of depression, was seen as an essential feature of both the model and a depressive state. The prolonged exposure of rodents to unpredictable/uncontrollable mild stressors leads to a reduction in the intake of palatable liquids, behavioral despair, locomotor inhibition, anxiety-like changes, and vegetative (somatic) abnormalities. Many of the CMS studies do not report these patterns of behaviors, and they often fail to include consistent molecular, neuroanatomical, and physiological phenotypes of CMS-exposed animals. Objectives To critically review the CMS studies in rats so that conceptual and methodological flaws can be avoided in future studies. Results Analysis of the literature supports the validity of the CMS model and its impact on the field. However, further improvements could be achieved by (i) the stratification of animals into ‘resilient’ and ‘susceptible’ cohorts within the CMS animals, (ii) the use of more refined protocols in the sucrose test to mitigate physiological and physical artifacts, and (iii) the systematic evaluation of the non-specific effects of CMS and implementation of appropriate adjustments within the behavioral tests. Conclusions We propose methodological revisions and the use of more advanced behavioral tests to refine the rat CMS paradigm, which offers a valuable tool for developing new antidepressant medications.

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Population Genomics, Transcriptional Response to Heat Shock, and Gut Microbiota of the Hong Kong Oyster Magallana hongkongensis - Yichun Xie; Elaine Y. Y. Huang; Wenyan Nong; Sean T. S. Law; Yifei Yu; Khan Cheung; Yiqian Li; Cheuk Fung Wong; Ho Yin Yip; Patrick W. S. Joyce; King Ming Chan; Ka Hou Chu; et al. (Journal of Marine Science and Engineering, 2022)
The Hong Kong oyster Magallana hongkongensis, previously known as Crassostrea hongkongensis, is a true oyster species native to the estuarine-coast of the Pearl River Delta in southern China. The species—with scientific, ecological, cultural, and nutritional importance—has been farmed for hundreds of years. However, there is only limited information on its genetics, stress adaptation mechanisms, and gut microbiota, restricting the sustainable production and use of oyster resources. Here, we present population structure analysis on M. hongkongensis oysters collected from Deep Bay and Lantau Island in Hong Kong, as well as transcriptome analysis on heat shock responses and the gut microbiota profile of M. hongkongensis oysters collected from Deep Bay. Single nucleotide polymorphisms (SNPs), including those on the homeobox genes and heat shock protein genes, were revealed by the whole genome resequencing. Transcriptomes of oysters incubated at 25 °C and 32 °C for 24 h were sequenced which revealed the heat-induced regulation of heat shock protein pathway genes. Furthermore, the gut microbe community was detected by 16S rRNA sequencing which identified Cyanobacteria, Proteobacteria and Spirochaetes as the most abundant phyla. This study reveals the molecular basis for the adaptation of the oyster M. hongkongensis to environmental conditions.

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Bioinformatic analyses suggest augmented interleukin-17 signaling as the mechanism of COVID-19-associated herpes zoster - Xin Yu; Linfeng Li; Matthew T. V. Chan; William Ka Kei Wu (Environmental Science and Pollution Research, 2021)

Household environmental microbiota influences early‐life eczema development - Le Duc Huy Ta; Carina Jing Xuan Tay; Christophe Lay; Paola Florez de Sessions; Cheryl Pei Ting Tan; Michelle Jia Yu Tay; Hui Xing Lau; Atiqa Binte Zulkifli; Gaik Chin Yap; Elizabeth Huiwen Tham; Eliza Xin Pei Ho; Anne Eng Neo Goh; et al. (Environmental Microbiology, 2021)
Summary Exposure to a diverse microbial environment during pregnancy and early postnatal period is important in determining predisposition towards allergy. However, the effect of environmental microbiota exposure during preconception, pregnancy and postnatal life on development of allergy in the child has not been investigated so far. In the S‐PRESTO (Singapore PREconception Study of long Term maternal and child Outcomes) cohort, we collected house dust during all three critical window periods and analysed microbial composition using 16S rRNA gene sequencing. At 6 and 18 months, the child was assessed for eczema by clinicians. In the eczema group, household environmental microbiota was characterized by presence of human‐associated bacteria Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium at all time points, suggesting their possible contributions to regulating host immunity and increasing the susceptibility to eczema. In the home environment of the control group, putative protective effect of an environmental microbe Planomicrobium ( Planococcaceae family) was observed to be significantly higher than that in the eczema group. Network correlation analysis demonstrated inverse relationships between beneficial Planomicrobium and human‐associated bacteria ( Actinomyces , Anaerococcus, Finegoldia, Micrococcus, Prevotella and Propionibacterium ). Exposure to natural environmental microbiota may be beneficial to modulate shed human‐associated microbiota in an indoor environment.

A critical review of microplastic pollution in urban freshwater environments and legislative progress in China: Recommendations and insights - Yuyao Xu; Faith Ka Shun Chan; Jun He; Matthew Johnson; Christopher Gibbins; Paul Kay; Thomas Stanton; Yaoyang Xu; Gang Li; Meili Feng; Odette Paramor; Xubiao Yu; et al. (Critical Reviews in Environmental Science and Technology, 2021)

Genomic characterization of a rare Carica papaya X chromosome mutant reveals a candidate monodehydroascorbate reductase 4 gene involved in all-hermaphrodite phenomenon - Jen-Ren Chen; Hiroki Ueno; Hideo Matsumura; Naoya Urasaki; Chen-Yu Lee; Fure-Chyi Chen; Shih-Wen Chin; Chun-Chi Liu; Chan-Tai Chiu; Kazuhiko Tarora; Jing-Yi Li; Chieh Ying Lee; et al. (Molecular Genetics and Genomics, 2021)

Dynamic monitoring of surface water in the Tibetan Plateau from 1980s to 2019 based on satellite remote sensing images - Hui-chan Liu; Guo-jin He; Yan Peng; Gui-zhou Wang; Ran-yu Yin (Journal of Mountain Science, 2021)

Three-dimensional Spheroid Culture Enhances Multipotent Differentiation and Stemness Capacities of Human Dental Pulp‐derived Mesenchymal Stem Cells by Modulating MAPK and NF-kB Signaling Pathways - Ya-Hui Chan; Yu-Chieh Lee; Chia-Yi Hung; Pi-Ju Yang; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2021)

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

Microscopic and molecular detection of Eimeria maxima and Eimeria praecox naturally infected in free-range village chickens of Myanmar - Saw Bawm; Shwe Yee Win; Nyein Chan Soe; Yu Nandi Thaw; Myint Myint Hmoon; Lat Lat Htun; Ryo Nakao; Ken Katakura (Acta Parasitologica, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Preparation and Characterization of a Lutein Solid Dispersion to Improve Its Solubility and Stability - Chaemin Lim; Jin Kook Kang; Chan Eun Jung; Taehoon Sim; Jaewon Her; Kioh Kang; Eun Seong Lee; Yu Seok Youn; Han-Gon Choi; Kyung Taek Oh (AAPS PharmSciTech, 2021)

Parental whole life cycle exposure modulates progeny responses to ocean acidification in slipper limpets - Elizaldy A. Maboloc; Kit Yu Karen Chan (Global Change Biology, 2021)
Multigenerational exposure is needed to assess the evolutionary potential of organisms in the rapidly changing seascape. Here, we investigate if there is a transgenerational effect of ocean acidification exposure on a calyptraeid gastropod such that long‐term exposure elevates offspring resilience. Larvae from wild type Crepidula onyx adults were reared from hatching until sexual maturity for over 36 months under three pH conditions (pH 7.3, 7.7, and 8.0). While the survivorship, growth, and respiration rate of F 1 larvae were unaffected by acute ocean acidification (OA), long‐term and whole life cycle exposure significantly compromised adult survivorship, growth, and reproductive output of the slipper limpets. When kept under low pH throughout their life cycle, only 6% of the F 1 slipper limpets survived pH 7.3 conditions after ~2.5 years and the number of larvae they released was ~10% of those released by the control. However, the F 2 progeny from adults kept under the long‐term low pH condition hatched at a comparable size to those in medium and control pH conditions. More importantly, these F 2 progeny from low pH adults outperformed F 2 slipper limpets from control conditions; they had higher larval survivorship and growth, and reduced respiration rate across pH conditions, even at the extreme low pH of 7.0. The intragenerational negative consequences of OA during long‐term acclimation highlights potential carryover effects and ontogenetic shifts in stress vulnerability, especially prior to and during reproduction. Yet, the presence of a transgenerational effect implies that this slipper limpet, which has been widely introduced along the West Pacific coasts, has the potential to adapt to rapid acidification.

Synthesis of Thresholds of Ocean Acidification Impacts on Echinoderms - Nina Bednaršek; Piero Calosi; Richard A. Feely; Richard Ambrose; Maria Byrne; Kit Yu Karen Chan; Sam Dupont; Jacqueline L. Padilla-Gamiño; John I. Spicer; Faycal Kessouri; Miranda Roethler; Martha Sutula; et al. (Frontiers in Marine Science, 2021)
Assessing the vulnerability of marine invertebrates to ocean acidification (OA) requires an understanding of critical thresholds at which developmental, physiological, and behavioral traits are affected. To identify relevant thresholds for echinoderms, we undertook a three-step data synthesis, focused on California Current Ecosystem (CCE) species. First, literature characterizing echinoderm responses to OA was compiled, creating a dataset comprised of >12,000 datapoints from 41 studies. Analysis of this data set demonstrated responses related to physiology, behavior, growth and development, and increased mortality in the larval and adult stages to low pH exposure. Second, statistical analyses were conducted on selected pathways to identify OA thresholds specific to duration, taxa, and depth-related life stage. Exposure to reduced pH led to impaired responses across a range of physiology, behavior, growth and development, and mortality endpoints for both larval and adult stages. Third, through discussions and synthesis, the expert panel identified a set of eight duration-dependent, life stage, and habitat-dependent pH thresholds and assigned each a confidence score based on quantity and agreement of evidence. The thresholds for these effects ranged within pH from 7.20 to 7.74 and duration from 7 to 30 days, all of which were characterized with either medium or low confidence. These thresholds yielded a risk range from early warning to lethal impacts, providing the foundation for consistent interpretation of OA monitoring data or numerical ocean model simulations to support climate change marine vulnerability assessments and evaluation of ocean management strategies. As a demonstration, two echinoderm thresholds were applied to simulations of a CCE numerical model to visualize the effects of current state of pH conditions on potential habitat.

Spatial distributions of metal(loid)s and their transport in agricultural soils around abandoned metal mine sites in South Korea - Sung-Wook Yun; Duck-Kyu Choi; Chan Yu (Journal of Soils and Sediments, 2021)

Deformation patterns and potential active movements of the Fansipan mountain range, northern Vietnam - Thi-Hue Dinh; Yu-Chang Chan; Chung-Pai Chang; Chih-Tung Chen; Yi-Chun Hsu (International Journal of Earth Sciences, 2021)

Study on Influence of Construction Process of Double-Line Shield Tunnels on Frame Structure - Hui Yang; Hongtao Shi; Xueliang Jiang; Chan Liu; Lei Yu (Geotechnical and Geological Engineering, 2021)

Identification through fine mapping and verification using CRISPR/Cas9-targeted mutagenesis for a minor QTL controlling grain weight in rice - Aye Nyein Chan; Lin-Lin Wang; Yu-Jun Zhu; Ye-Yang Fan; Jie-Yun Zhuang; Zhen-Hua Zhang (Theoretical and Applied Genetics, 2021)
Key message A minor QTL for grain weight in rice, qTGW1.2b , was fine-mapped. Its casual gene OsVQ4 was confirmed through CRISPR/Cas9-targeted mutagenesis, exhibiting an effect that was larger than the original QTL effect. Abstract The CRISPR/Cas system exhibits a great potential for rice improvement, but the application was severely hindered due to insufficient target genes, especial the lack of validated genes underlying quantitative trait loci having small effects. In this study, a minor QTL for grain weight, qTGW1.2b , was fine-mapped into a 44.0 kb region using seven sets of near isogenic lines (NILs) developed from the indica rice cross (Zhenshan 97) 3 /Milyang 46, followed by validation of the causal gene using CRISPR/Cas9-targeted mutagenesis. In the NIL populations, 1000-grain weight of the Zhenshan 97 homozygous lines decreased by 0.9–2.0% compared with the Milyang 46 homozygous lines. A gene encoding VQ-motif protein, OsVQ4 , was identified as the candidate gene based on parental sequence differences. The effect of OsVQ4 was confirmed by creating CRISPR/Cas9 knockout lines, whose 1000-grain weight decreased by 2.8–9.8% compared with the wild-type transgenic line and the recipient. These results indicate that applying genome editing system could create novel alleles with large phenotypic variation at minor QTLs, which is an effective way to validate causal genes of minor QTLs. Our study establishes a strategy for cloning minor QTLs, which could also be used to identify a large number of potential target genes for the application of CRISPR/Cas system.

Predicting Functional Outcome Based on Linked Data After Acute Ischemic Stroke: S-SMART Score - Tae Jung Kim; Ji Sung Lee; Mi-Sun Oh; Ji-Woo Kim; Jae Sun Yoon; Jae-Sung Lim; Chan-Hyuk Lee; Heejung Mo; Han-Yeong Jeong; Yerim Kim; Sang-Hwa Lee; Keun-Hwa Jung; et al. (Translational Stroke Research, 2020)

Identification of Functional SSR Markers in Freshwater Ornamental Shrimps Neocaridina denticulata Using Transcriptome Sequencing - Chang-Wen Huang; Pei-Yun Chu; Yu-Fang Wu; Wei-Ren Chan; Yeh-Hao Wang (Marine Biotechnology, 2020)

Coupled numerical simulation of a flexible barrier impacted by debris flow with boulders in front - L. Zhao; J. W. He; Z. X. Yu; Y. P. Liu; Z. H. Zhou; S. L. Chan (Landslides, 2020)

Resilience of invasive tubeworm (Hydroides dirampha) to warming and salinity stress and its implications for biofouling community dynamics - Ting-Xuan Liu; Seneca Kinn-Gurzo; Kit Yu Karen Chan (Marine Biology, 2020)

Cytotoxic triquinane-type sesquiterpenoids from the endophytic fungus Cerrena sp. A593 - Hong-Xin Liu; Hai-Bo Tan; Yu-Chan Chen; Sai-Ni Li; Hao-Hua Li; Wei-Min Zhang (Natural Product Research, 2020)

An Insight into Diversity and Functionalities of Gut Microbiota in Insects - Shengchen Wang; Luyi Wang; Xian Fan; Chan Yu; Liang Feng; Li Yi (Current Microbiology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Investigating the effects of clay/sand content on depositional mechanisms of submarine debris flows through physical and numerical modeling - Dingzhu Liu; Yifei Cui; Jian Guo; Zhilin Yu; Dave Chan; Mingyu Lei (Landslides, 2020)

Functional responses between PMP3 small membrane proteins and membrane potential - Alvin C. M. Kwok; Fang Zhang; Zhiyi Ma; Wai Sun Chan; Vivian C. Yu; Jimmy S. H. Tsang; Joseph T. Y. Wong (Environmental Microbiology, 2020)
Summary The Plasma Membrane Proteolipid 3 (PMP3, UPF0057 family in Uniprot) family consists of abundant small hydrophobic polypeptides with two predicted transmembrane helices. Plant homologues were upregulated in response to drought/salt‐stresses and yeast deletion mutants exhibited conditional growth defects. We report here abundant expression of Group I PMP3 homologues (PMP3(i)hs) during normal vegetative growth in both prokaryotic and eukaryotic cells, at a level comparable to housekeeping genes, implicating the regular cellular functions. Expression of eukaryotic PMP3 (i)hs was dramatically upregulated in response to membrane potential (Vm) variability (Vm var ), whereas PMP3 (i)hs deletion‐knockdown led to Vm changes with conditional growth defects. Bacterial PMP3(i)h yqaE deletion led to a shift of salt sensitivity; Vm var alternations with exogenous K + addition downregulated prokaryotic PMP3(i)hs, suggesting [K + ]‐Vm var axis being a significant feedback element in prokaryotic ionic homeostasis. Remarkably, the eukaryotic homologues functionally suppressed the conditional growth defects in bacterial deletion mutant, demonstrating the conserved cross‐kingdom membrane functions by PMP3(i)hs. These data demonstrated a direct reciprocal relationship between PMP3(i)hs expression and Vm differentials in both prokaryotic and eukaryotic cells. Cumulative with PMP3(i)hs ubiquitous abundance, their lipid‐binding selectivity and membrane protein colocalization, we propose [PMP3(i)hs]‐Vm var axis as a key element in membrane homeostasis.

Spatial Variation in Thermal Stress Experienced by Barnacles on Rocky Shores: The Interplay Between Geographic Variation, Tidal Cycles and Microhabitat Temperatures - Hui-Yu Wang; Ling Ming Tsang; Fernando P. Lima; Rui Seabra; Monthon Ganmanee; Gray A. Williams; Benny K. K. Chan (Frontiers in Marine Science, 2020)

A new butenolide derivative from the deep-sea fungus Aspergillus terreus SCSIO FZQ028 - Qi Zeng; Wei-Mao Zhong; Yu-Chan Chen; Yao Xiang; Xia-Yu Chen; Xin-Peng Tian; Wei-Min Zhang; Si Zhang; Fa-Zuo Wang (Natural Product Research, 2020)

Correction to: How whale and dolphin barnacles attach to their hosts and the paradox of remarkably versatile attachment structures in cypris larvae - Niklas Dreyer; John D. Zardus; Jens T. Høeg; Jørgen Olesen; Meng-Chen Yu; Benny K. K. Chan (Organisms Diversity & Evolution, 2020)

How whale and dolphin barnacles attach to their hosts and the paradox of remarkably versatile attachment structures in cypris larvae - Niklas Dreyer; John D. Zardus; Jens T. Høeg; Jørgen Olesen; Meng-Chen Yu; Benny K. K. Chan (Organisms Diversity & Evolution, 2020)

Global distribution of the intensity and frequency of hourly precipitation and their responses to ENSO - Xiao-Feng Li; Stephen Blenkinsop; Renaud Barbero; Jingjing Yu; Elizabeth Lewis; Geert Lenderink; Selma Guerreiro; Steven Chan; Yafei Li; Haider Ali; Roberto Villalobos Herrera; Elizabeth Kendon; et al. (Climate Dynamics, 2020)
We investigate the global distribution of hourly precipitation and its connections with the El Niño–Southern Oscillation (ENSO) using both satellite precipitation estimates and the global sub-daily rainfall gauge dataset. Despite limited moisture availability over continental surfaces, we find that the highest mean and extreme hourly precipitation intensity (HPI) values are mainly located over continents rather than over oceans, a feature that is not evident in daily or coarser resolution data. After decomposing the total precipitation into the product of the number of wet hours (NWH) and HPI, we find that ENSO modulates total precipitation mainly through the NWH, while its effects on HPI are more limited. The contrasting responses to ENSO in NWH and HPI is particularly apparent at the rising branches of the Pacific and Atlantic Walker Circulations, and is also notable over land-based gauges in Australia, Malaysia, the USA, Japan and Europe across the whole distribution of hourly precipitation (i.e. extreme, moderate and light precipitation). These results provide new insights into the global precipitation distribution and its response to ENSO forcing.

Potential for short-term migration of mineral oil hydrocarbons from coated and uncoated food contact paper and board into a fatty food simulant - Eun Chul Pack; Dae Yong Jang; Min Gi Cha; Ye Ji Koo; Hyung Soo Kim; Hong Hyeon Yu; Seok Chan Park; Young Soon Kim; Kyung Min Lim; Seung Ha Lee; Dal Woong Choi (Food Additives & Contaminants: Part A, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

An alternative splicing variant of mineralocorticoid receptor discovered in preeclampsia tissues and its effect on endothelial dysfunction - Mengxi Guo; Chengliang Zhou; Gufeng Xu; Lin Tang; Yechun Ruan; Ying Yu; Xianhua Lin; Dandan Wu; Hao Chen; Priscilla Yu; Luyang Jin; Yinyu Wang; et al. (Science China Life Sciences, 2020)

Correction to: Population Pharmacokinetics, Efficacy Exposure-response Analysis, and Model-based Meta-analysis of Fenebrutinib in Subjects with Rheumatoid Arthritis - Phyllis Chan; Jiajie Yu; Leslie Chinn; Marita Prohn; Jan Huisman; Brett Matzuka; William Hanley; Katie Tuckwell; Angelica Quartino (Pharmaceutical Research, 2020)

Population Pharmacokinetics, Efficacy Exposure-response Analysis, and Model-based Meta-analysis of Fenebrutinib in Subjects with Rheumatoid Arthritis - Phyllis Chan; Jiajie Yu; Leslie Chinn; Marita Prohn; Jan Huisman; Brett Matzuka; William Hanley; Katie Tuckwell; Angelica Quartino (Pharmaceutical Research, 2020)
Purpose Fenebrutinib (GDC-0853), a Bruton’s tyrosine kinase (BTK) inhibitor was investigated in a Phase 2 clinical trial in patients with rheumatoid arthritis (RA). Our aim was to apply a model-informed drug development (MIDD) approach to examine the totality of available clinical efficacy data. Methods Population pharmacokinetics (popPK) modeling, exposure-response (E-R) analysis, and model-based meta-analysis (MBMA) of fenebrutinib were performed based on the Phase 2 data. Results PopPK of fenebrutinib after oral administration was described using a 3-compartment model with linear elimination and a flexible absorption transit compartment model. Healthy subjects had a 52% higher apparent clearance than patients. E-R analyses based on longitudinal ACR20, ACR50, and ACR70 and DAS28 (CRP) data modeled fenebrutinib effect with an E max function, and an efficacy plateau was achieved within the exposure range obtained in the Phase 2 clinical trial. Based on literature data, a summary-level clinical efficacy database was constructed, and MBMA determined ACR20, ACR50, and ACR70 responder rates in the placebo and adalimumab arms of the Phase 2 clinical trial were found to be consistent with historical data for these treatments. Conclusions Our multi-pronged approach applied MIDD to maximize knowledge extraction of efficacy data and enabled robust interpretation from a Phase 2 clinical trial.

Vertical distribution of echinoid larvae in pH stratified water columns - Elizaldy A. Maboloc; Grant Batzel; Daniel Grünbaum; Kit Yu Karen Chan (Marine Biology, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Flavobacterium sangjuense sp. nov. isolated from sediment - Hyangmi Kim; Sun-Yeon Heo; Jee-Hwan Kim; Jong-Chan Chae; Sang Mi Yu (Antonie van Leeuwenhoek, 2019)

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment - Di Yu; Marie Hennebelle; Demetrios J. Sahlas; Joel Ramirez; Fuqiang Gao; Mario Masellis; Hugo Cogo-Moreira; Richard H. Swartz; Nathan Herrmann; Pak Cheung Chan; Jacqueline A. Pettersen; Donald T. Stuss; et al. (Translational Stroke Research, 2019)

Contrasting forms of competition set elevational range limits of species - Shih‐Fan Chan; Wei‐Kai Shih; An‐Yu Chang; Sheng‐Feng Shen; I‐Ching Chen (Ecology Letters, 2019)
How abiotic and biotic factors constrain distribution limits at the harsh and benign edges of species ranges is hotly debated, partly because macroecological experiments testing the proximate causes of distribution limits are scarce. It has long been recognized – at least since Darwin’s On the Origin of Species – that a harsh climate strengthens competition and thus sets species range limits. Using thorough field manipulations along a large elevation gradient, we show the mechanisms by which temperature determines competition type, resulting in a transition from interference to exploitative competition from the lower to the upper elevation limits in burying beetles ( Nicrophorus nepalensis ). This transition is an example of Darwin’s classic hypothesis that benign climates favor direct competition for highly accessible resources while harsh climates result in competition through resources of high rivalry. We propose that identifying the properties of these key resources will provide a more predictive framework to understand the interplay between biotic and abiotic factors in determining geographic range limits.

Biomarker-based Seawater Temperatures of Winter Sinking Particles and Core-top Sediment in the Ulleung Basin of the East Sea - Yu-Hyeon Park; Hyung Jeek Kim; Ju Won Son; Chan Min Yoo; Boo-Keun Khim (Ocean Science Journal, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Feasibility of Two-Dimensional Radiation Dose Distribution Simulation Through Ultrasound Tracking of Respiratory Motion - Chia-Chun Kuo; Ho-Chiao Chuang; Chan-Yang Kuo; Lai-Lei Ting; Hsiao-Wei Yu; Yu-Peng Wu; Hsiao-Yu Hsu; Der-Chi Tien; Shiu-Chen Jeng; Jeng-Fong Chiou (Journal of Medical and Biological Engineering, 2019)

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Transcriptomic responses of the marine cyanobacterium Prochlorococcus to viral lysis products - Xiaoting Fang; Yaxin Liu; Yao Zhao; Yue Chen; Riyue Liu; Qi‐Long Qin; Gang Li; Yu‐Zhong Zhang; Wan Chan; Wolfgang R. Hess; Qinglu Zeng (Environmental Microbiology, 2019)
Summary Viral infection of marine phytoplankton releases a variety of dissolved organic matter (DOM). The impact of viral DOM (vDOM) on the uninfected co‐occurring phytoplankton remains largely unknown. Here, we conducted transcriptomic analyses to study the effects of vDOM on the cyanobacterium Prochlorococcus , which is the most abundant photosynthetic organism on Earth. Using Prochlorococcus MIT9313, we showed that its growth was not affected by vDOM, but many tRNAs increased in abundance. We tested tRNA‐gly and found that its abundance increased upon addition of glycine. The decreased transcript abundances of N metabolism genes also suggested that Prochlorococcus responded to organic N compounds in vDOM. Addition of vDOM to Prochlorococcus reduced the maximum photochemical efficiency of photosystem II and CO 2 fixation while increasing its respiration rate, consistent with differentially abundant transcripts related to photosynthesis and respiration. One of the highest positive fold‐changes was observed for the 6S RNA, a noncoding RNA functioning as a global transcriptional regulator in bacteria. The high level of 6S RNA might be responsible for some of the observed transcriptional responses. Taken together, our results revealed the transcriptional regulation of Prochlorococcus in response to viral lysis products and suggested its metabolic potential to utilize organic N compounds.

Comparative physiological and metabolomic analyses reveal natural variations of tulip in response to storage temperatures - Yanping Wang; Huimin Zhao; Yaping Wang; Siyuan Yu; Yuchao Zheng; Wen’en Wang; Zhulong Chan (Planta, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Absence of Stress Response in Dorsal Raphe Nucleus in Modulator of Apoptosis 1-Deficient Mice - Hui Zhao; Nur-Ezan Mohamed; Su Jing Chan; Chong Teik Tan; Ran Tao; Victor C. Yu; Peter T.-H. Wong (Molecular Neurobiology, 2019)

Studies on flexible rockfall barriers for failure modes, mechanisms and design strategies: a case study of Western China - Z. X. Yu; L. Zhao; Y. P. Liu; S. C. Zhao; H. Xu; S. L. Chan (Landslides, 2019)

Understanding the Impacts of Surface Compositions on the In-Vitro Dissolution and Aerosolization of Co-Spray-Dried Composite Powder Formulations for Inhalation - Sharad Mangal; Rongkun Xu; Heejun Park; Dmitry Zemlyanov; Nivedita Shetty; Yu-Wei Lin; David Morton; Hak-Kim Chan; Jian Li; Qi Tony Zhou (Pharmaceutical Research, 2019)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Asian dust storms and diabetes hospitalization: a nationwide population-based study - Yun-Shan Chan; Joshua Chen-Yuan Teng; Tsai-Ching Liu; Yu-I Peng (Air Quality, Atmosphere & Health, 2018)

Diurnal cycle of rainfall in amount, frequency, intensity, duration, and the seasonality over the UK - Chan Xiao; Weihua Yuan; Rucong Yu (International Journal of Climatology, 2018)
The diurnal variation of the rainfall amount, frequency and intensity, and the rainfall with different durations, as well as their seasonality, were analysed by using the hourly rainfall data at 90 stations in the UK during 1998–2015. The rainfall amount averaged in the entire UK presented two comparable peaks in the early morning and the late afternoon, which contributed by the frequency (the early morning) and the intensity (the late afternoon), separately. The rainfall peaks were closely related with the location and the duration of the rainfall. For the rainfall amount, the early morning peaks were more prevailing in the rainfall events lasting more than 6 hr and at the stations along the western coast of the British Isles; however, the rainfall events lasting 1–6 hr usually reached the hourly maximum in the late afternoon. For the seasonal variability, more nocturnal rainfall peaks of rainfall amount and intensity were found over the southern plains in winter. In spring to autumn, only the rainfall at some coastal stations or the stations on islands got the maximum during midnight to the early morning. For the rainfall frequency, the regional differences were more apparent in spring and summer, and the hourly rainfall frequency in the UK mainly peaked around 0600 GMT (Greenwich mean time) in autumn and in 1100–1300 GMT in winter. The results enriched the knowledge of the hourly rainfall features over the UK.

Secondary metabolites from the Colletotrichum gloeosporioides A12, an endophytic fungus derived from Aquilaria sinensis - Hong-Xin Liu; Hai-Bo Tan; Yu-Chan Chen; Sai-Ni Li; Hao-Hua Li; Wei-Min Zhang (Natural Product Research, 2018)

Quetiapine ameliorates collagen-induced arthritis in mice via the suppression of the AKT and ERK signaling pathways - Yi-Ju Pan; Wei-Hsun Wang; Tzu-Yao Huang; Wei-Hsiang Weng; Chun-Kai Fang; Yu-Chan Chen; Jeng-Jong Hwang (Inflammation Research, 2018)

Application of Ultrasound Image Tracking Algorithm for Real-Time Diaphragmatic Excursion Measurement - Chan-Yang Kuo; Ho-Chiao Chuang; Yi-Liang Zhou; Yu-Peng Wu; Jia-Chang Wang; Chia-Chun Kuo; Shiu-Chen Jeng; Hung-Wen Kao; Ming-Yuan Huang; Jeng-Fong Chiou; Ai-Ho Liao (Journal of Medical and Biological Engineering, 2018)

Comparison of short-term associations with meteorological variables between COPD and pneumonia hospitalization among the elderly in Hong Kong—a time-series study - Holly Ching-yu Lam; Emily Ying-yang Chan; William Bernard Goggins (International Journal of Biometeorology, 2018)

Mechanical and Clinical Evaluation of a Shape Memory Alloy and Conventional Struts in a Flexible Scoliotic Brace - Wing-Yu Chan; Joanne Yip; Kit-Lun Yick; Sun-Pui Ng; Lu Lu; Kenneth Man-Chee Cheung; Kenny Yat-Hong Kwan; Jason Pui-Yin Cheung; Kelvin Wai-Kwok Yeung; Chi-Yung Tse (Annals of Biomedical Engineering, 2018)

Immune consequences induced by photodynamic therapy in non-melanoma skin cancers: a review - Xin Yu; Heyi Zheng; Matthew T. V. Chan; William K. K. Wu (Environmental Science and Pollution Research, 2018)

Characterization of Deep-sea Macrofauna in the Korean Exploration Claim Area in the Clarion-Clipperton Fracture Zone, Northeastern Pacific Ocean - Ok Hwan Yu; Hyung-Gon Lee; Dongsung Kim; Jin Hee Wi; Kyeong Hong Kim; Chan Min Yoo (Ocean Science Journal, 2018)

Tectonic implications of Mesozoic magmatism to initiation of Cenozoic basin development within the passive South China Sea margin - Hue Anh Mai; Yu Lu Chan; Meng Wan Yeh; Tung Yi Lee (International Journal of Earth Sciences, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Interactive effects of temperature and salinity on early life stages of the sea urchin Heliocidaris crassispina - Karen Kiu-Yan Mak; Kit Yu Karen Chan (Marine Biology, 2018)

Descriptions of two new species of Xarifia copepods (Copepoda: Xarifiidae) with a key to the known species associated with the coral family, Euphylliidae Alloiteau, 1952 - Yu-Rong Cheng; Benny K. K. Chan (Marine Biodiversity, 2018)

Slip monitoring of a dip-slope and runout simulation by the discrete element method: a case study at the Huafan University campus in northern Taiwan - Chia-Han Tseng; Yu-Chang Chan; Ching-Jiang Jeng; Yu-Chung Hsieh (Natural Hazards, 2017)

Genomic clues to the parental origin of the wild flowering cherry Prunus yedoensis var. nudiflora (Rosaceae) - Ara Cho; Seunghoon Baek; Goon-Bo Kim; Chang-Ho Shin; Chan-Soo Kim; Kyung Choi; Youngje Kang; Hee-Ju Yu; Joo-Hwan Kim; Jeong-Hwan Mun (Plant Biotechnology Reports, 2017)

Acute Exposure to Pacific Ciguatoxin Reduces Electroencephalogram Activity and Disrupts Neurotransmitter Metabolic Pathways in Motor Cortex - Gajendra Kumar; Ngan Pan Bennett Au; Elva Ngai Yu Lei; Yim Ling Mak; Leanne Lai Hang Chan; Michael Hon Wah Lam; Leo Lai Chan; Paul Kwan Sing Lam; Chi Him Eddie Ma (Molecular Neurobiology, 2017)

Effect of Relative Humidity on Bipolar Electrostatic Charge Profiles of dry Powder Aerosols - Jiaqi Yu; Jennifer Wong; Ari Ukkonen; Jonna Kannosto; Hak-Kim Chan (Pharmaceutical Research, 2017)

Newcastle disease virus-like particles induce dendritic cell maturation and enhance viral-specific immune response - Jing Qian; Jiaxin Ding; Renfu Yin; Yixue Sun; Cong Xue; Xiaohong Xu; Jianzhong Wang; Chan Ding; Shengqing Yu; Xiufan Liu; Shunlin Hu; Yanlong Cong; et al. (Virus Genes, 2017)

A new cycloartane-type triterpenoid from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Chu-Wen Li; Jian-Bo Sun; Yu Chang; Judy Yuet-Wa Chan; Simon Ming-Yuan Lee; Bao Zeng (Natural Product Research, 2017)

Propagation and synchronization of reverberatory bursts in developing cultured networks - Chih-Hsu Huang; Yu-Ting Huang; Chun-Chung Chen; C. K. Chan (Journal of Computational Neuroscience, 2017)

A 15.4-ka paleoclimate record inferred from δ13C and δ15N of organic matter in sediments from the sub-alpine Daping Swamp, western Nanling Mountains, South China - Wei Zhong; Zhiqiang Wei; Yu Chen; Shengtan Shang; Jibin Xue; Jun Ouyang; Jiayuan Cao; Bin Chen; Chan Zhu (Journal of Paleolimnology, 2017)

Genetic diversity of the genotype VII Newcastle disease virus: identification of a novel VIIj sub-genotype - Cong Xue; Yanlong Cong; Renfu Yin; Yixue Sun; Chan Ding; Shengqing Yu; Xiufan Liu; Shunlin Hu; Jing Qian; Qianliang Yuan; Mingxi Yang; Chunfeng Wang; et al. (Virus Genes, 2017)

Constituents from the leaves of Clausena lansium and their anti-inflammatory activity - De-Yang Shen; Ping-Chung Kuo; Shiow-Chyn Huang; Tsong-Long Hwang; Yu-Yi Chan; Po-Chuen Shieh; Nguyen Thi Ngan; Tran Dinh Thang; Tian-Shung Wu (Journal of Natural Medicines, 2017)

Cellular degradation activity is maintained during aging in long-living queen bees - Chin-Yuan Hsu; Jiantai Timothy Qiu; Yu-Pei Chan (Biogerontology, 2016)

Indoxyl sulfate enhances IL-1β-induced E-selectin expression in endothelial cells in acute kidney injury by the ROS/MAPKs/NFκB/AP-1 pathway - Wen-Ching Shen; Chan-Jung Liang; Tao-Ming Huang; Chen-Wei Liu; Shu-Huei Wang; Guang-Huar Young; Jaw-Shiun Tsai; Ying-Chin Tseng; Yu-Sen Peng; Vin-Cent Wu; Yuh-Lien Chen (Archives of Toxicology, 2016)

Pigmentation effect of electromagnetic fields at various intensities to melanocytes - Sang-Eun Cho; Yu-Mi Kim; Kye-Hong Kang; Soo-Chan Kim; Jung-Keug Park; Young-Kwon Seo (Tissue Engineering and Regenerative Medicine, 2016)

The modulation of Th2 immune pathway in the immunosuppressive effect of human umbilical cord mesenchymal stem cells in a murine asthmatic model - Chin-Kan Chan; Ting-Chun Lin; Yung-An Huang; Ya-Shan Chen; Chia-Ling Wu; Huei-Yu Lo; Ming-Ling Kuo; Kang-Hsi Wu; Jing-Long Huang (Inflammation Research, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

How Much Surface Coating of Hydrophobic Azithromycin Is Sufficient to Prevent Moisture-Induced Decrease in Aerosolisation of Hygroscopic Amorphous Colistin Powder? - Qi Zhou; Zhi Hui Loh; Jiaqi Yu; Si-ping Sun; Thomas Gengenbach; John A. Denman; Jian Li; Hak-Kim Chan (The AAPS Journal, 2016)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Identification and functional analysis of phosphorylation in Newcastle disease virus phosphoprotein - Xusheng Qiu; Yuan Zhan; Chunchun Meng; Junqing Wang; LuNa Dong; Yingjie Sun; Lei Tan; Cuiping Song; Shengqing Yu; Chan Ding (Archives of Virology, 2016)

Application of Short-Time MSE in Assessing Impact of Acupuncture on Peripheral Blood Flow and Autonomic Activities in Normal and Overweight Subjects - Cheng-Chan Yang; Hsien-Tsai Wu; Wei-Yu Chuang; Te-Chun Liu; I-Ting Tsai; Jian-Jung Chen; Cheuk-Kwan Sun (Journal of Medical and Biological Engineering, 2016)

Draft Genome Sequence of Neisseria gonorrhoeae Strain NG_869 with Penicillin, Tetracycline and Ciprofloxacin Resistance Determinants Isolated from Malaysia - Geik Yong Ang; Choo Yee Yu; Delicia Ann Yong; Yuet Meng Cheong; Wai-Fong Yin; Kok-Gan Chan (Indian Journal of Microbiology, 2016)

Use of the Biopharmaceutics Drug Disposition Classification System (BDDCS) to Help Predict the Occurrence of Idiosyncratic Cutaneous Adverse Drug Reactions Associated with Antiepileptic Drug Usage - Rosa Chan; Chun-yu Wei; Yuan-tsong Chen; Leslie Z. Benet (The AAPS Journal, 2016)

Simultaneous GC-MS determination of seven phthalates in total and migrated portions of paper cups - Yu Na Park; Min Sun Choi; Shaheed Ur Rehman; Myung Chan Gye; Hye Hyun Yoo (Environmental Science and Pollution Research, 2016)

Resistance to viral yellow leaf curl in tomato through RNAi targeting two Begomovirus species strains - Huei-mei Chen; Chen-yu Lin; Wen-shi Tsai; Lawrence Kenyon; Ming-tsair Chan; Jo-yi Yen; Shao-yu Chang; Robert de la Peña; Roland Schafleitner (Journal of Plant Biochemistry and Biotechnology, 2016)

Sleep education in Hong Kong - Ngan Yin Chan; Siu Ping Lam; Jihui Zhang; Mandy Wai Man Yu; Shirley Xin Li; Albert Martin Li; Yun Kwok Wing (Sleep and Biological Rhythms, 2016)

FBXW7-Induced MTOR Degradation Forces Autophagy to Counteract Persistent Prion Infection - Yin Xu; Chan Tian; Jing Sun; Jin Zhang; Ke Ren; Xue-Yu Fan; Ke Wang; Hui Wang; Yu-E Yan; Cao Chen; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2016)

Role of Rho Kinase and Fasudil on Synaptic Plasticity in Multiple Sclerosis - Chan Chen; Jie-Zhong Yu; Qiong Zhang; Yong-Fei Zhao; Chun-Yun Liu; Yan-Hua Li; Wan-Fang Yang; Cun-Gen Ma; Bao-Guo Xiao (NeuroMolecular Medicine, 2015)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

In Vivo Sodium MRI for Mouse Model of Ischemic Stroke at 7 T: Preliminary Results - Kun-Che Lee; Jen-Fang Yu; Yi-Shin Lee; Guo-Jen Huang; Hsiao-Lung Chan; In-Tsang Lin; Jyh-Honrg Chen (Journal of Medical and Biological Engineering, 2015)

Improved antioxidant activity in transgenic Perilla frutescens plants via overexpression of the γ-tocopherol methyltransferase (γ-tmt) gene - Bimal Kumar Ghimire; Eun Soo Seong; Chan Ok Lee; Jae Geun Lee; Chang Yeon Yu; Seung Hyun Kim; Ill Min Chung (Protoplasma, 2015)

Multi-Scale Modelling of Powder Dispersion in a Carrier-Based Inhalation System - Zhenbo Tong; Hidehiro Kamiya; Aibing Yu; Hak-Kim Chan; Runyu Yang (Pharmaceutical Research, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Groundwater arsenic removal using granular TiO2: integrated laboratory and field study - Jinli Cui; Jingjing Du; Siwu Yu; Chuanyong Jing; Tingshan Chan (Environmental Science and Pollution Research, 2015)

Characterization of the chaperonin GroEL in Mycoplasma gallisepticum - Lei Tan; Meirong Hu; Shengqing Yu; Xin Wang; Feng Lu; Fang Liu; Xusheng Qiu; Cuiping Song; Yingjie Sun; Chan Ding (Archives of Microbiology, 2015)

Bromodeoxyuridine labelling and fluorescence‐activated cell sorting of polyamine‐transforming bacterioplankton in coastal seawater - Xiaozhen Mou; Jisha Jacob; Xinxin Lu; Maria Vila‐Costa; Leong‐Keat Chan; Shalabh Sharma; Yu‐qin Zhang (Environmental Microbiology, 2015)
Summary Polyamines ( PAs ) are a group of nitrogen‐rich dissolved organic nitrogen ( DON ) compounds that are ubiquitously distributed in marine environments. To identify bacteria that are involved in PA transformations, coastal bacterioplankton microcosms were amended with a single PA model compound, i.e. putrescine ( PUT ) or spermidine ( SPD ), or with no addition as controls ( CTRs ). Bromodeoxyuridine ( BrdU ) was added to all the microcosms to label newly synthesized DNAs . Fluorescence‐activated cell sorting ( FACS ) analysis indicated significant increases in numbers of total cells and cells with both high and low levels of BrdU incorporation in the PUT and SPD microcosms, but not in the CTRs . 16 S rDNA pyrotag sequencing of FACS ‐sorted cells indicated that PUT ‐ and SPD ‐transforming bacteria were composed similarly of a diverse group of taxa affiliated with A ctinobacteria , B acteroidetes , F irmicutes and P roteobacteria (especially R oseobacter of its alpha lineage). Broad taxonomic distribution of PA ‐transforming bacteria was also indicated by the abundance and distribution of PA transporter gene homologues in a survey of sequenced marine bacterial genomes. Our results suggest that PAs may be common DON substrates for marine bacterioplankton, in line with the hypothesis that bacterially mediated PA transformation accounts for an important proportion of marine DON flux.

Development of a reverse genetics system based on RNA polymerase II for Newcastle disease virus genotype VII - Jianzhong Wang; Chunfeng Wang; Na Feng; Hualei Wang; Xuexing Zheng; Songtao Yang; Yuwei Gao; Xianzhu Xia; Renfu Yin; Xiufan Liu; Shunlin Hu; Chan Ding; et al. (Virus Genes, 2015)

The leaching characteristics of Cd, Zn, and As from submerged paddy soil and the effect of limestone treatment - Sung-Wook Yun; Chan Yu (Paddy and Water Environment, 2015)

Proteomic analysis of CD44(+) and CD44(−) gastric cancer cells - Dayeon Yu; Hyun-Soo Shin; Go Choi; Yong Chan Lee (Molecular and Cellular Biochemistry, 2014)

Polycyclic Aromatic Hydrocarbons Degrading Microflora in a Tropical Oil-Production Well - Chan Yu; Jun Yao; Minmin Cai; Haiyan Yuan; Huilun Chen; Brunello Ceccanti (Bulletin of Environmental Contamination and Toxicology, 2014)

Toll-like receptor 3 inhibits Newcastle disease virus replication through activation of pro-inflammatory cytokines and the type-1 interferon pathway - Jinghua Cheng; Yingjie Sun; Xiaorong Zhang; Fanqing Zhang; Shilei Zhang; Shengqing Yu; Xusheng Qiu; Lei Tan; Cuiping Song; Song Gao; Yantao Wu; Chan Ding (Archives of Virology, 2014)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Remarkable reductions of PAKs in the brain tissues of scrapie-infected rodent possibly linked closely with neuron loss - Ge Meng; Chan Tian; Hui Wang; Yin Xu; Bao-Yun Zhang; Qi Shi; Chen Gao; Cao Chen; Xue-Yu Fan; Jing Wang; Kang Xiao; Ke Ren; et al. (Medical Microbiology and Immunology, 2014)

Liposomal Co-Delivery of Omacetaxine Mepesuccinate and Doxorubicin for Synergistic Potentiation of Antitumor Activity - Gayong Shim; Sangbin Lee; Junhyeok Choi; Soondong Lee; Chan-Wha Kim; Yu-Kyoung Oh (Pharmaceutical Research, 2014)

Evaluate the heavy metal toxicity to Pseudomonas fluorescens in a low levels of metal-chelates minimal medium - Fei Wang; Jun Yao; Huilun Chen; Zhengji Yi; Chan Yu; Yujie Tuo; Lan Ma; Qian Yu (Environmental Science and Pollution Research, 2014)

Characterization of the immunogenicity and pathogenicity of malate dehydrogenase in Brucella abortus - Xiangan Han; Yongliang Tong; Mingxing Tian; Xiaoqing Sun; Shaohui Wang; Chan Ding; Shengqing Yu (World Journal of Microbiology and Biotechnology, 2014)

Basal cGMP regulates the resting pacemaker potential frequency of cultured mouse colonic interstitial cells of Cajal - Pawan Kumar Shahi; Seok Choi; Yu Jin Jeong; Chan Guk Park; Insuk So; Jae Yeoul Jun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Effect of age on the pathogenesis of DHV-1 in Pekin ducks and on the innate immune responses of ducks to infection - Cuiping Song; Shengqing Yu; Yunbing Duan; Yue Hu; Xvsheng Qiu; Lei Tan; Yingjie Sun; Mingshu Wang; Anchun Cheng; Chan Ding (Archives of Virology, 2014)

Significant Reduction of the GLUT3 Level, but not GLUT1 Level, Was Observed in the Brain Tissues of Several Scrapie Experimental Animals and Scrapie-Infected Cell Lines - Yu-E Yan; Jin Zhang; Ke Wang; Yin Xu; Ke Ren; Bao-Yun Zhang; Ming Shi; Cao Chen; Qi Shi; Chan Tian; Gang Zhao; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Overexpression of p62/SQSTM1 promotes the degradations of abnormally accumulated PrP mutants in cytoplasm and relieves the associated cytotoxicities via autophagy–lysosome-dependent way - Yin Xu; Jin Zhang; Chan Tian; Ke Ren; Yu-E Yan; Ke Wang; Hui Wang; Cao Chen; Jing Wang; Qi Shi; Xiao-Ping Dong (Medical Microbiology and Immunology, 2014)

Emodin elicits cytotoxicity in human lung adenocarcinoma A549 cells through inducing apoptosis - Wing-Yan Li; Yam-Fung Ng; Huan Zhang; Zi-Dong Guo; De-Jian Guo; Yiu-Wa Kwan; George Pak-Heng Leung; Simon Ming-Yuen Lee; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2014)

Investigating Pseudomonas putida–Candida humicola Interactions as Affected by Chelate Fe(III) in Soil - Fei Wang; Jun Yao; Chan Yu; Huilun Chen; Zhengji Yi (Bulletin of Environmental Contamination and Toxicology, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Isolation and characterization of a newly isolated pyrene-degrading Acinetobacter strain USTB-X - Haiyan Yuan; Jun Yao; Kanaji Masakorala; Fei Wang; Minmin Cai; Chan Yu (Environmental Science and Pollution Research, 2014)

Synergistic Antibiotic Combination Powders of Colistin and Rifampicin Provide High Aerosolization Efficiency and Moisture Protection - Qi Zhou; Thomas Gengenbach; John A. Denman; Heidi H. Yu; Jian Li; Hak Kim Chan (The AAPS Journal, 2014)

Terfenadine induces anti-proliferative and apoptotic activities in human hormone-refractory prostate cancer through histamine receptor-independent Mcl-1 cleavage and Bak up-regulation - Wei-Ting Wang; Yen-Hui Chen; Jui-Ling Hsu; Wohn-Jenn Leu; Chia-Chun Yu; She-Hung Chan; Yunn-Fang Ho; Lih-Ching Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Tissue-based environmental quality benchmarks and standards - James P. Meador; Michael St. J. Warne; Peter M. Chapman; King Ming Chan; Shen Yu; Kenneth M. Y. Leung (Environmental Science and Pollution Research, 2014)

Silicic acid supplied to coastal diatom communities influences cellular silicification and the potential export of carbon - Colleen A. Durkin; Sara J. Bender; Kit Yu Karen Chan; Kelsey Gaessner; Daniel Grünbaum; E. Virginia Armbrust (Limnology and Oceanography, 2013)
Microcosm experiments were conducted along the Washington and Oregon coasts in May 2009, May 2010, and July 2010 to determine whether variation in the supply of silicic acid from the Columbia River could influence the silicification and sinking potential of coastal diatom blooms. The chlorophyll a concentration increased similarly in communities incubated with added nitrate or both nitrate and silicic acid, indicating that growth was limited by nitrate availability. Communities that grew in the treatment with added silicic acid and nitrate were more silicified than communities in the treatment with only nitrate added. No difference in community composition was detected between these treatments in three out of four experiments. Isolates of Minutocellus , Cylindrotheca , Thalassiosira , and Odontella were obtained from the microcosm experiment conducted in May 2010 and were maintained in the laboratory in 20 µmol L −1 silicic acid. All four diatom isolates contained ∼ 2.5 times more silica per cell when silicic acid concentration in the media was increased to 80 µmol L −1 . The intensity of a fluorescent cellular stain of newly precipitated silica (2‐(4‐pyridyl)‐5{[4‐dimethylaminoethyl‐aminocarbamoyl)‐methoxy]phenyl}oxazole) strongly correlated with silica content among species, but was a less sensitive indicator of changing silicification within a single species. Changes in silicification were not correlated with changes in the transcript abundance of silicic acid transporters. Sinking rates increased roughly 2‐fold for cells that contained ∼ 2.5 times more silica. Variation in silicic acid supply alters the silicification of nitrate‐fueled coastal diatom blooms and the potential sink of carbon from coastal zones.

Ocean acidification induces budding in larval sea urchins - Kit Yu Karen Chan; Daniel Grünbaum; Maj Arnberg; Michael Thorndyke; Sam T. Dupont (Marine Biology, 2013)

Effects of Petroleum Hydrocarbon Contaminated Soil on Germination, Metabolism and Early Growth of Green Gram, Vigna radiata L. - Kanaji Masakorala; Jun Yao; Radhika Chandankere; Haiyan Yuan; Haijun Liu; Chan Yu; Minmin Cai (Bulletin of Environmental Contamination and Toxicology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Sesamin extends the mean lifespan of fruit flies - Yuanyuan Zuo; Cheng Peng; Yintong Liang; Ka Ying Ma; Ho Yin Edwin Chan; Yu Huang; Zhen-Yu Chen (Biogerontology, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

Enhanced apoptosis in retinal pigment epithelium under inflammatory stimuli and oxidative stress - Yujuan Wang; Defen Shen; Vinson M. Wang; Cheng-Rong Yu; Ren-Xi Wang; Jingsheng Tuo; Chi-Chao Chan (Apoptosis, 2012)

Characteristics and sources of non-methane hydrocarbons and halocarbons in wintertime urban atmosphere of Shanghai, China - Ping Song; Fu-Hai Geng; Xue-Fang Sang; Chuen-Yu Chan; Lo-Yin Chan; Qiong Yu (Environmental Monitoring and Assessment, 2012)

Stream discharge characteristics through urbanization gradient in Danshui River, Taiwan: perspectives from observation and simulation - Jr-Chuan Huang; Chun-Chiang Lin; Shih-Chien Chan; Tsung-Yu Lee; Shih-Chieh Hsu; Cheing-Tung Lee; Jiun-Chuan Lin (Environmental Monitoring and Assessment, 2012)

Electronegative low-density lipoprotein induces cardiomyocyte apoptosis indirectly through endothelial cell-released chemokines - An-Sheng Lee; Guei-Jane Wang; Hua-Chen Chan; Fang-Yu Chen; Chia-Ming Chang; Chao-Yuh Yang; Yuan-Teh Lee; Kuan-Cheng Chang; Chu-Huang Chen (Apoptosis, 2012)

Novel ionic liquid supported-multicomponent reaction toward chimeric bis-heterocycles - Chih-Hau Chen; Chan-Yu Chen; Po-Tsung Lin; Chung-Ming Sun (Molecular Diversity, 2012)

Association of promoter region single nucleotide polymorphisms at positions −819C/T and −592C/A of interleukin 10 gene with ischemic heart disease - Gyeong-Im Yu; Ho-Chan Cho; Yun-Kyeong Cho; Hyoung-Seob Park; Hyuck-Jun Yoon; Hyung-Seop Kim; Chang-Wook Nam; Yoon-Nyun Kim; Kwon-Bae Kim; Eunyoung Ha; Dong-Hoon Shin; Seung-Ho Hur (Inflammation Research, 2012)

Ds transposon is biased towards providing splice donor sites for exonization in transgenic tobacco - Kuo-Chan Huang; Hsiu-Chun Yang; Kuan-Te Li; Li-yu Daisy Liu; Yuh-Chyang Charng (Plant Molecular Biology, 2012)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Synthesis of a ligand–quencher conjugate for the ligand binding study of the aryl hydrocarbon receptor using a FRET assay - Yu Wang; Dazhou Yang; Abraham Chang; William K. Chan; Bin Zhao; Michael S. Denison; Liang Xue (Medicinal Chemistry Research, 2012)

Newcastle disease virus triggers autophagy in U251 glioma cells to enhance virus replication - Chunchun Meng; Zhizhi Zhou; Ke Jiang; Shengqing Yu; Lijun Jia; Yantao Wu; Yanqing Liu; Songshu Meng; Chan Ding (Archives of Virology, 2012)

Whole genome sequencing and biological characterization of Duck/JS/10, a new lentogenic class I Newcastle disease virus - Chunchun Meng; Xvsheng Qiu; Shiqiang Jin; Shengqing Yu; Hongjun Chen; Chan Ding (Archives of Virology, 2012)

Enzymatic and biological characteristics of enolase in Brucella abortus A19 - Xiangan Han; Chan Ding; Hongjun Chen; Qinghai Hu; Shengqing Yu (Molecular Biology Reports, 2012)

Reconstructed light extinction coefficients using chemical compositions of PM2.5 in winter in Urban Guangzhou, China - Jun Tao; Jun-Ji Cao; Ren-Jian Zhang; Lihua Zhu; Tao Zhang; Si Shi; Chuen-Yu Chan (Advances in Atmospheric Sciences, 2012)

Mutations in the NRG1 gene are associated with Hirschsprung disease - Clara Sze-Man Tang; Elly Sau-Wai Ngan; Wai-Kiu Tang; Man-Ting So; Guo Cheng; Xiao-Ping Miao; Thomas Yuk-Yu Leon; Brian Man-Chun Leung; Kenneth-Jeremy W. S. Hui; Vincent Hang-Chai Lui; Yan Chen; Ivy Hau-Yee Chan; et al. (Human Genetics, 2012)

Levoglucosan and carbonaceous species in the background aerosol of coastal southeast China: case study on transport of biomass burning smoke from the Philippines - Yi-Nan Zhang; Zhi-Sheng Zhang; Chuen-Yu Chan; Guenter Engling; Xue-Fang Sang; Si Shi; Xue-Mei Wang (Environmental Science and Pollution Research, 2012)

Cationic Liposomal Co-delivery of Small Interfering RNA and a MEK Inhibitor for Enhanced Anticancer Efficacy - Seung Hee Kang; Hee-Jeong Cho; Gayong Shim; Sangbin Lee; Su-Hyeon Kim; Han-Gon Choi; Chan-Wha Kim; Yu-Kyoung Oh (Pharmaceutical Research, 2011)

In Vitro and In Vivo Investigation of Drug-Eluting Implants for the Treatment of Periodontal Disease - Fu-Ying Lee; Dave W. Chen; Chih-Chien Hu; Yu-Te Hsieh; Shih-Jung Liu; Err-Cheng Chan (AAPS PharmSciTech, 2011)

Discrepancies between global reanalyses and observations in the interdecadal variations of Southeast Asian cold surge - Wan‐Ru Huang; Shih‐Yu Wang; Johnny C. L. Chan (International Journal of Climatology, 2011)
The Siberian High (SH) is an important part of the East Asian winter monsoon (EAWM) and is closely linked to cold surges. Previous studies revealed a pronounced decline in the strength of the SH during the late 20th century accompanied with a coherent decrease in the frequency of cold surges. However, studies using different data sets yielded different behaviour of the trends. Here we examine the interdecadal variations of the SH and cold surges deduced from six modern global reanalysis data sets. Discrepancies in such variations are found between the reanalysis data sets and observations as well as among different reanalysis data sets. Such discrepancies contribute to inconsistent interdecadal variations of the cold surge frequency in different reanalysis data sets. Potential causes of this situation are discussed. Copyright © 2010 Royal Meteorological Society

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

The determinants of serum vitamin D levels in participants in a melanoma case–control study living in a temperate climate - John R. Davies; Yu-Mei Chang; Helen Snowden; May Chan; Susan Leake; Birute Karpavicius; Sue Haynes; Kairen Kukalizch; Juliette Randerson-Moor; Faye Elliott; Julian Barth; Peter A. Kanetsky; et al. (Cancer Causes & Control, 2011)

Manganese Superoxide Dismutase Deficiency Exacerbates Ischemic Brain Damage Under Hyperglycemic Conditions by Altering Autophagy - Suresh L. Mehta; Yanling Lin; Wenge Chen; Fengshan Yu; Luyi Cao; Qingping He; Pak H. Chan; P. Andy Li (Translational Stroke Research, 2011)

Optimal design and impact analysis of urban traffic regulations under ambient uncertainty - Yu-Ta Wu; Kuei-Yuan Chan (Stochastic Environmental Research and Risk Assessment, 2011)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Precipitation characteristics in the Three Gorges Dam vicinity - Chan Xiao; Rucong Yu; Yunfei Fu (International Journal of Climatology, 2010)
After the building of the Three Gorges Dam (TGD), the water level abruptly rose from 66 to 135 m in June 2003, and the land use characteristics changed significantly throughout the TGD region. More and more people are concerned with the effect of the TGD reservoir on climate. In this paper, the decadal variation of precipitation in the vicinity of the TGD was analysed using daily data from 27 rain gauges from 1960 to 2005. The empirical orthogonal function (EOF) analysis of annual precipitation anomalies indicates a clear difference in spatial distribution, with an opposite signal for the change in precipitation in the northern and southern areas of the Yangtze River, i.e. precipitation increases in the northern area are accompanied with decreases in the southern area and vice versa. The similar dipole pattern of precipitation variation around the TGD also occurred before the TGD, for example, in the period from 1977 to 1984. Therefore, it has not been shown with reasonable significance that the similar dipole pattern of precipitation variation around the TGD has been affected by the TGD. Copyright © 2009 Royal Meteorological Society

Construction of mini-Tn4001 transposon vector for Mycoplasma gallisepticum - HongJun Chen; ChunMei Zhao; XieYue Shen; DanQing Chen; ShengQing Yu; Chan Ding (Science China Life Sciences, 2010)

The Removal of Ocular Artifacts from EEG Signals Using Adaptive Filters Based on Ocular Source Components - Hsiao-Lung Chan; Yu-Tai Tsai; Ling-Fu Meng; Tony Wu (Annals of Biomedical Engineering, 2010)

A Novel Cytoplasmic Isopentenyl Diphosphate Isomerase Gene from Tomato (Solanum lycopersicum): Cloning, Expression, and Color Complementation - Jin Sun; Yu-Yang Zhang; Hui Liu; Zhe Zou; Chan-Juan Zhang; Xiao-Hui Zhang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Cloning, expression and characterization of xylose isomerase, XylA, from Caldanaerobacter subterraneus subsp. yonseiensis - Byoung-Chan Kim; Sun Nyoung Yu; Kwang Youn Kim; Jung Sook Lee; Yu-Ryang Pyun; Soon Cheol Ahn (Biotechnology Letters, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Pseudonocardia rhizophila sp. nov., a novel actinomycete isolated from a rhizosphere soil - Jie Li; Guo-Zhen Zhao; Hai-Yu Huang; Wen-Yong Zhu; Jae-Chan Lee; Chang-Jin Kim; Li-Hua Xu; Li-Xin Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2010)

Mesoscale vortex generation and merging process: A case study associated with a post-landfall tropical depression - Zifeng Yu; Xudong Liang; Hui Yu; Johnny C. L. Chan (Advances in Atmospheric Sciences, 2010)

Preface - Masaru Terabayashi; Kazuaki Okamoto; Hiroshi Yamamoto; Yu‐Chang Chan (Island Arc, 2010)

Genome-wide discovery of DNA polymorphism in Brassica rapa - Soomin Park; Hee-Ju Yu; Jeong-Hwan Mun; Seung-Chan Lee (Molecular Genetics and Genomics, 2010)

Effects of puerarin on receptor for advanced glycation end products in nephridial tissue of streptozotocin-induced diabetic rats - Jian Guo Shen; Mei Fen Yao; Xiao Chan Chen; Yun Fei Feng; Yu Hong Ye; Zhong Hang Tong (Molecular Biology Reports, 2009)

Cloning, characterization and expression analysis of a CXCR1-like gene from mandarin fish Siniperca chuatsi - Chao Chen; Zhongsheng Li; Zhicheng Zhou; Zhixin Yin; Siu-Ming Chan; Xiao-Qiang Yu; Shaoping Weng; Jianguo He (Fish Physiology and Biochemistry, 2009)

Identification and characterization of the duck enteritis virus UL51 gene - Chan-Juan Shen; An-Chun Cheng; Ming-Shu Wang; Yu-Fei Guo; Li-Chan Zhao; Ming Wen; Wei Xie; Hong-Yi Xin; De-Kang Zhu (Archives of Virology, 2009)

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Formulation Development and Bioavailability Evaluation of a Self-Nanoemulsified Drug Delivery System of Oleanolic Acid - Jia Xi; Qi Chang; Chak K. Chan; Zhao Yu Meng; Geng Nan Wang; Jia Bei Sun; Yi Tao Wang; Henry H. Y. Tong; Ying Zheng (AAPS PharmSciTech, 2009)

Heavy Metal Contamination of Arable Soil and Corn Plant in the Vicinity of a Zinc Smelting Factory and Stabilization by Liming - Chang Oh Hong; Jessie Gutierrez; Sung Wook Yun; Yong Bok Lee; Chan Yu; Pil Joo Kim (Archives of Environmental Contamination and Toxicology, 2009)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

Role of MyD88 in TLR agonist-induced functional alterations of human adipose tissue-derived mesenchymal stem cells - Sungsook Yu; Hyun Hwa Cho; Hye Joon Joo; Yong Chan Bae; Jin Sup Jung (Molecular and Cellular Biochemistry, 2008)

Antioxidative activities and the total phenolic contents of tonic Chinese Medicinal Herbs - D.-J. Guo; H.-L. Cheng; S.-W. Chan; P. H.-F. Yu (Inflammopharmacology, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

Role of CD9 in proliferation and proangiogenic action of human adipose-derived mesenchymal stem cells - Yeon Jeong Kim; Ji Min Yu; Hye Joon Joo; Hoe Kyu Kim; Hyun Hwa Cho; Yong Chan Bae; Jin Sup Jung (Pflügers Archiv - European Journal of Physiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

A simulation study on pre-landfall erratic track of typhoon Haitang (2005) - H. Yu; W. Huang; Y. H. Duan; J. C. L. Chan; P. Y. Chen; R. L. Yu (Meteorology and Atmospheric Physics, 2007)

Do medical students in Hong Kong have enough sleep? - Lok-Lam E HUEN; Tze-Wai G CHAN; Wai-Man M YU; Yun-Kwok WING (Sleep and Biological Rhythms, 2007)

Production of d-tagatose at high temperatures using immobilized Escherichia coli cells expressing l-arabinose isomerase from Thermotoga neapolitana - Young-Ho Hong; Dong-Woo Lee; Sang-Jae Lee; Eun-Ah Choe; Seong-Bo Kim; Yoon-Hee Lee; Chan-Ick Cheigh; Yu-Ryang Pyun (Biotechnology Letters, 2007)

Bacterial siderophores: the solution stoichiometry and coordination of the Fe(III) complexes of pyochelin and related compounds - Chiu-Fou Tseng; Alain Burger; Gaëtan L. A. Mislin; Isabelle J. Schalk; Steve S.-F. Yu; Sunney I. Chan; Mohamed A. Abdallah (JBIC Journal of Biological Inorganic Chemistry, 2006)

Burrow Architecture of the Ghost Crab Ocypode ceratophthalma on a Sandy Shore in Hong Kong - Benny Kwok Kan Chan; Karen Kit Yu Chan; Philip Cheuk Man Leung (Hydrobiologia, 2006)

Toluene exposure during the brain growth spurt reduces behavioral responses to noncompetitive N-methyl-d-aspartate receptor antagonists in adult rats - Te-Hsiung Chien; Ming-Huan Chan; Yu-Chi Tang; Hwei-Hsien Chen (Psychopharmacology, 2005)

Nisin Biosynthesis and its Properties - Chan-Ick Cheigh; Yu-Ryang Pyun (Biotechnology Letters, 2005)

Caenorhabditis elegans gcs-1 Confers Resistance to Arsenic-Induced Oxidative Stress - Vivian Hsiu-Chuan Liao; Chan-Wei Yu (BioMetals, 2005)

A population-based LD map of the human chromosome 6p - Hong Xiang Yu; Jer-Ming Chia; Guillaume Bourque; Marie Vivien Wong; Soh Ha Chan; Ee Chee Ren (Immunogenetics, 2005)

A Novel Oscillating Bioreactor BelloCell: Implications for Insect Cell Culture and Recombinant Protein Production - Jen-Te Lu; Yao-Chi Chung; Zun-Ren Chan; Yu-Chen Hu (Biotechnology Letters, 2005)

Candidate gene database and transcript map for peach, a model species for fruit trees - Renate Horn; Anne-Claire Lecouls; Ann Callahan; Abhaya Dandekar; Lilibeth Garay; Per McCord; Werner Howad; Helen Chan; Ignazio Verde; Doreen Main; Sook Jung; Laura Georgi; et al. (Theoretical and Applied Genetics, 2005)

Detecting Epstein-Barr virus DNA from peripheral blood mononuclear cells in adult patients with systemic lupus erythematosus in Taiwan - Shan-Fu Yu; Huei-Chuin Wu; Wen-Chan Tsai; Jeng-Hsien Yen; Wen Chiang; Chung-Yee Yuo; Sheng-Nan Lu; Lien-Chai Chiang; Chung-Jen Chen (Medical Microbiology and Immunology, 2005)

The effect of salinity on trichloroethylene co-metabolism by mixed cultures enriched on phenol - Chi-Yuan Lee; Yu-Chia Chan; Chin-Lung Lin (World Journal of Microbiology and Biotechnology, 2005)

Enhanced nisin production by increasing genes involved in nisin Z biosynthesis in Lactococcus lactis subsp. lactis A164 - Chan-Ick Cheigh; Hoon Park; Hak-Jong Choi; Yu-Ryang Pyun (Biotechnology Letters, 2005)

Heat stress response in plants: a complex game with chaperones and more than twenty heat stress transcription factors - Sanjeev Kumar Baniwal; Kapil Bharti; Kwan Yu Chan; Markus Fauth; Arnab Ganguli; Sachin Kotak; Shravan Kumar Mishra; Lutz Nover; Markus Port; Klaus-Dieter Scharf; Joanna Tripp; Christian Weber; et al. (Journal of Biosciences, 2004)

Expression of TRPC homologs in endothelial cells and smooth muscle layers of human arteries - Ham Yip; Wing-Yee Chan; Pan-Cheung Leung; Hiu-Yee Kwan; Cuiling Liu; Yu Huang; Villaz Michel; David Tai-Wai Yew; Xiaoqiang Yao (Histochemistry and Cell Biology, 2004)

Involvement of NO/cGMP pathway in toluene-induced locomotor hyperactivity in female rats - Ming-Huan Chan; Te-Hsiung Chien; Pei-Yu Lee; Hwei-Hsien Chen (Psychopharmacology, 2004)

Simple one-step purification of nisin Z from unclarified culture broth of Lactococcus lactis subsp. lactis A164 using expanded bed ion exchange chromatography - Chan-Ick Cheigh; Moo-Chang Kook; Seong-Bo Kim; Young-Ho Hong; Yu-Ryang Pyun (Biotechnology Letters, 2004)

Concentration Level of Fine Airborne Lead in Beijing, People?s Republic of China - K. B. He; F. K. Duan; Y. L. Ma; F. M. Yang; Q. Zhang; X. C. Yu; S. Cadle; T. Chan; Y. Yan; P. Mulawa (Bulletin of Environmental Contamination and Toxicology, 2004)

The role of β-effect and a uniform current on tropical cyclone intensity - Yihong Duan; Rongsheng Wu; Hui Yu; Xudong Liang; Johnny C. L. Chan (Advances in Atmospheric Sciences, 2004)

Preparation and Characterization of Reconstructed Small Intestinal Brush Border Membranes for Surface Plasmon Resonance Analysis - Sungpil Cho; Jae Hyung Park; Jaehoon Yu; Yong-Kyu Lee; Youngro Byun; Hesson Chung; Ick Chan Kwon; Seo Young Jeong (Pharmaceutical Research, 2004)

Expression of olfactory-type cyclic nucleotide-gated channel (CNGA2) in vascular tissues - Kwong-Tai Cheng; Franky Leung Chan; Yu Huang; Wing-Yee Chan; Xiaoqiang Yao (Histochemistry and Cell Biology, 2003)

The mechanism of honokiol-induced and magnolol-induced inhibition on muscle contraction and Ca 2+ mobilization in rat uterus - Yu-Cheng Lu; Hwei-Hsien Chen; Chien-Hsin Ko; Yi-Ruu Lin; Ming-Huan Chan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Regulation of the Expression of the Prostate-specific Antigen by Claudin-7 - J. -Y. Zheng; D. Yu; M. Foroohar; E. Ko; J. Chan; N. Kim; R. Chiu; S. Pang (The Journal of Membrane Biology, 2003)

Native-feather degradation by Fervidobacterium islandicum AW-1, a newly isolated keratinase-producing thermophilic anaerobe - Gae-Won Nam; Dong-Woo Lee; Han-Seoung Lee; Nam-Ju Lee; Byoung-Chan Kim; Eun-Ah Choe; Jae-Kwan Hwang; Maggy Suhartono; Yu-Ryang Pyun (Archives of Microbiology, 2002)

Random antisense cDNA mutagenesis as an efficient functional genomic approach in higher plants - Ji Jun; Cheol Kim; Dae Cho; June Kwak; Chan Ha; Yu Park; Baik Cho; David Patton; Hong Nam (Planta, 2002)

Abolition of endothelium-dependent relaxation in the rat aorta by tetraoctylammonium ions - Yu Huang; X.Q. Yao; F.L. Chan; C.W. Lau; N.W.K. Chan; Z.Y. Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

A comparison of sampling designs in a Hainan tropical rain forest - S. X. Yu; H. S. Y. Chan; K. W. Chung (Community Ecology, 2000)

Influence of Cr3+ on microbial cluster formation in biofilm and on steel corrosion - Herbert H.P. Fang; Li-Chong Xu; Kwong-Yu Chan (Biotechnology Letters, 2000)

NBl-C16-Insulin: Site-Specific Synthesis, Purification, and Biological Activity - Hong Mei; X. Christopher Yu; Kenneth K. Chan (Pharmaceutical Research, 1999)

Ultrastructural and biochemical observations on the early changes in apoptotic epithelial cells of the rat prostate induced by castration - Joseph Kwong; H.L. Choi; Yu Huang; Franky L. Chan (Cell and Tissue Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

An efficient protocol for sugarcane (Saccharum spp. L.) transformation mediated by Agrobacterium tumefaciens - Ariel D. Arencibia; Elva R. Carmona; Pilar Tellez; Ming-Tsair Chan; Su-May Yu; Luis E. Trujillo; Pedro Oramas (Transgenic Research, 1998)

Cymbidium mosaic potexvirus RNA: complete nucleotide sequence and phylogenetic analysis - S. M. Wong; P. H. Mahtani; K. C. Lee; H. H. Yu; Y. Tan; K. K. Neo; Y. Chan; M. Wu; C. G. Chng (Archives of Virology, 1997)

Identification of a cDNA encoding 6-phosphogluconate dehydrogenase from a human heart cDNA library - Stephen Kwok Wing Tsui; Judy Yuet Wa Chan; Mary Miu Yee Waye; Kwok Pui Fung; Cheuk Yu Lee (Biochemical Genetics, 1996)

Studies on cellulase production by a Bacillus subtilis - Kwong-Yu Chan; K. S. Au (Antonie van Leeuwenhoek, 1987)

The effects of diesel oil and oil dispersants on growth, photosynthesis, and respiration ofChlorella salina - Kwong -yu Chan; S. Y. Chiu (Archives of Environmental Contamination and Toxicology, 1985)